Laminated polyester film
By forming a resin layer containing microparticles on the polyester film, the flatness and smoothness problems during winding are solved, the processing performance and production efficiency of the polyester film are improved, and the coating shedding and contamination are reduced.
Patent Information
- Application Number
- JP2023120139
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
Smart Images

Figure 2025017184000012 
Figure 2025017184000001 
Figure 2025017184000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated polyester film. [Background technology]
[0002] Polyester films, typified by polyethylene terephthalate films and polyethylene naphthalate films, have excellent properties such as mechanical properties, dimensional stability, flatness, heat resistance, chemical resistance, optical properties, etc., and also have excellent cost performance, so they are used for various purposes.
[0003] In addition, polyester films are favorably used for various release applications, such as release films for molding green sheets for multilayer ceramic capacitors, interlayer insulating resin release films, and release films for dry film resists, taking advantage of the smoothness of the film surface.
[0004] Release films for sheet molding having excellent surface smoothness for the above-mentioned applications and other uses are required to be wrinkle-free and have a good roll appearance when wound into a roll. However, increasing the surface smoothness reduces the slipperiness and reduces the ability of the film to escape air when wound into a roll or when unwound from the roll, resulting in slippage and blocking, which reduces the handling properties. In particular, in recent years, with the improvement in productivity, there has been a trend toward thinner and longer release films, which requires a higher level of roll appearance quality.
[0005] Therefore, in order to ensure ease of handling, for example in the case of release films used to mold green sheets for multilayer ceramic capacitors, the side opposite to the side on which the polyester film release layer is provided, i.e., the non-smooth side (back side), is sometimes designed to be rougher than the smooth side by kneading particles into it (e.g., Patent Document 1). Furthermore, Patent Document 2 discloses a slippery composite polyester film in which a continuous coating layer having a fine mesh uneven structure is provided on at least one surface of a polyester film for the purpose of improving handling properties. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-33811 A [Patent Document 2] JP 2000-211082 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the conventional method for producing a particle-incorporated film as disclosed in Patent Document 1, it is difficult to control the formation of unevenness, making it difficult to form a fine uneven structure, and in the film disclosed in Patent Document 2, the unevenness is insufficient, so that wrinkles tend to occur when the film is wound into a roll, which can impair the appearance of the roll. Furthermore, for example, in the manufacturing process of green sheets for multilayer ceramic capacitors, there are problems such as the inherent performance of the laminated polyester film being impaired due to peeling or falling off of the coating film, and the manufacturing process being contaminated by the fallen coating film. Therefore, in laminated polyester films, there are cases where adhesion and cohesion between the base film and the coating film formed thereon is also required, and there are also cases where the coating film is required to be less likely to fall off, i.e., the retention rate of the coating film is high.
[0008] Therefore, the present invention has been made in consideration of the above-mentioned situation, and the problem to be solved by this invention is to provide a laminated polyester film that has excellent handling properties, for example, when the film is wound into a roll, by forming a fine surface structure in the resin layer. Another object of the present invention is to provide a laminated polyester film which has a high coating film retention rate and is resistant to peeling. [Means for solving the problem]
[0009] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by the following configuration. The present invention has the following aspects.
[0010] [1] A laminated polyester film having a resin layer formed from a resin composition on at least one surface of a polyester film, the resin layer containing particles, and the average length of the roughness curve element (RSm) of the surface of the resin layer being 5 μm or more. [2] The laminated polyester film according to the above [1], wherein the kurtosis (Sku) of the surface of the resin layer is less than 3. [3] The laminated polyester film according to the above [1] or [2], wherein the content of the particles in the resin layer is 10% by mass or more. [4] The laminated polyester film according to any one of the above [1] to [3], wherein the resin composition contains a binder resin (A). [5] The laminated polyester film according to any one of the above [1] to [4], wherein the resin composition contains a crosslinking agent (B). [6] The laminated polyester film according to any one of the above [1] to [5], wherein the load length ratio (Rmr(70)) of the roughness curve at a cutting level of 70% of the surface of the resin layer is 75% or less when measured with a scanning probe microscope. [7] The laminated polyester film according to any one of the above [1] to [6], wherein the resin layer has an uneven structure. [8] The laminated polyester film according to any one of the above [1] to [7], wherein the resin layer has a surface having an arithmetic average roughness (Ra) of 10 nm or more as measured by a scanning probe microscope. [9] The laminated polyester film according to any one of the above [1] to [8], wherein the ten-point average roughness (Rzjis) of the surface of the resin layer as measured by a scanning probe microscope is 60 nm or more.
[10] The laminated polyester film according to any one of the above [1] to [9], wherein the root mean square gradient (Sdq) of the resin layer surface is 0.1 or more.
[11] The laminated polyester film according to any one of the above [1] to
[10] , wherein the developed interface area ratio (Sdr) of the resin layer surface is 0.5% or more.
[12] The laminated polyester film according to any one of the above [1] to
[11] , wherein the resin layer has a surface arithmetic mean height (Sa) of more than 25 nm.
[13] The laminated polyester film according to any one of the above [1] to
[12] , wherein the resin layer has a maximum peak height (Sp) of more than 500 nm on the surface.
[14] The laminated polyester film according to any one of the above [1] to
[13] , which has an air leakage index of 50,000 seconds or less.
[15] The laminated polyester film according to any one of the above [1] to
[14] , wherein the particles have an average particle size of 1 to 100 nm.
[16] The laminated polyester film according to any one of the above [1] to
[15] , wherein the particles contain at least one selected from the group consisting of silica, zirconium oxide, and titanium oxide.
[17] The laminated polyester film according to any one of the above [4] to
[16] , wherein the (A) binder resin comprises at least one resin selected from the group consisting of polyester resins, (meth)acrylic resins, and polyurethane resins.
[18] The laminated polyester film according to any one of the above [5] to
[17] , wherein the (B) crosslinking agent is a melamine compound.
[19] The laminated polyester film according to any one of the above [1] to
[18] , which has a release layer on the surface opposite to the resin layer.
[20] The laminated polyester film according to
[19] above, wherein the release layer is formed from a release agent composition containing a release agent, and the release agent contains one or more compounds selected from the group consisting of silicone compounds and compounds containing a long-chain alkyl group.
[21] The laminated polyester film according to any one of the above [1] to
[20] , which is used as a support for a ceramic green sheet in a production process of a laminated ceramic capacitor.
[22] Use of the laminated polyester film according to any one of the above [1] to
[21] as a support for a ceramic green sheet in a process for producing a laminated ceramic capacitor.
[23] A method for producing a ceramic green sheet, comprising coating a slurry containing a ceramic component on a surface of the laminated polyester film according to any one of the above [1] to
[21] opposite to the resin layer. Effect of the Invention
[0011] According to the present invention, a laminated polyester film is provided which has excellent handleability when the film is wound into a roll, etc., due to the formation of a fine surface structure in the resin layer.
[0012] Furthermore, according to the present invention, it is possible to provide a laminated film which has a high coating film retention rate and is resistant to peeling.
[0013] In addition, since the laminated polyester film of the present invention can form a fine uneven structure on the resin layer surface, when the film is used for sheet molding, for example, the extremely smooth film has the advantage of exhibiting good winding properties and being less likely to cause wrinkles even when wound into a roll.
[0014] Furthermore, since the resin layer of the laminated polyester film of the present invention can be made thin, it is also possible to accommodate thin and long laminated polyester films, which can contribute to improving productivity by reducing the frequency of changing product rolls during processing. [Brief description of the drawings]
[0015] [Figure 1] 1 is an image of the surface of the resin layer in Example 6 observed with a scanning probe microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Next, an example of an embodiment of the present invention will be described, however, the present invention is not limited to the embodiment described below.
[0017] In this specification, when the expression "(meth)acrylic" is used, "(meth)acrylic" means one or both of "acrylic" and "methacrylic". Similarly, "(meth)acrylic acid" means one or both of "acrylic acid" and "methacrylic acid", "(meth)acrylate" means one or both of "acrylate" and "methacrylate", and "(meth)acryloyl" means one or both of "acryloyl" and "methacryloyl". The same applies to the other terms.
[0018] <<<Laminated polyester film>>> The laminated polyester film of the present invention (hereinafter also referred to as "the present laminated polyester film") has a polyester film (hereinafter also referred to as "the present polyester film") and a resin layer (hereinafter also referred to as "the present resin layer") formed from a resin composition on at least one side of the polyester film.
[0019] The laminated structure of the present laminated polyester film may be a structure in which a resin layer is formed on one side of a polyester film and the surface of the polyester film is left as is on the other side, or a structure in which another layer is formed on the other side. Alternatively, a resin layer may be formed on both sides of a polyester film. Furthermore, the resin layer may be formed directly on the polyester film, or another layer may be provided between the polyester film and the resin layer. In the present invention, it is also preferable that the laminated polyester film has a resin layer on one side and a release layer on the opposite side.
[0020] <<Polyester film>> The polyester film serves as a substrate for the laminated polyester film. The polyester film may be a single layer or a multilayer. When the polyester film has a multilayer structure, the polyester film may have a two-layer structure, a three-layer structure, or a four-layer structure or more without departing from the gist of the present invention. The number of layers is not particularly limited. When the polyester film has a multi-layer structure of two or more layers, a two-kind three-layer structure or a three-kind three-layer structure is particularly preferable. When the polyester film has a multi-layer structure, it is also preferable that the polyester film has a structure in which surface layers are provided on both sides of an intermediate layer.
[0021] In particular, when utilizing the smoothness of the laminated polyester film, it is preferable that at least one side of the polyester film has excellent smoothness. Examples of such design methods include a method of designing the polyester film to have a single layer, two-kind three-layer, or three-kind three-layer structure so that both sides of the polyester film have excellent smoothness, and a method of designing the polyester film to have a three-kind three-layer structure so that one side of the polyester film has excellent smoothness and the other side has a different roughness.
[0022] The polyester film may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred. Of these, a biaxially stretched film is more preferred in terms of excellent balance of mechanical properties and flatness.
[0023] <Polyester> The polyester, which is the raw material of the polyester film, refers to a polymeric compound having continuous ester bonds in the main chain, and may be a homopolyester or a copolymer polyester. Specifically, a polyester obtained by polycondensation reaction of a dicarboxylic acid component and a diol component can be mentioned. In addition, it is preferable to use a polyester containing more than 50 mol% of an aromatic dicarboxylic acid or an aliphatic dicarboxylic acid when the dicarboxylic acid component is taken as 100 mol%.
[0024] Examples of the dicarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid, and aliphatic dicarboxylic acids such as adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, and ester derivatives thereof.
[0025] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-hexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol.
[0026] When the polyester is a homopolyester, it is preferably one obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic diol. As the aromatic dicarboxylic acid, preferably, terephthalic acid, 2,6-naphthalenedicarboxylic acid, etc. are mentioned, and as the aliphatic diol, preferably, ethylene glycol, diethylene glycol, 1,4-cyclohexanedimethanol, etc. are mentioned. As a representative homopolyester, polyethylene terephthalate (PET), polyethylene-2,6-naphthalenedicarboxylate (PEN), etc. can be mentioned, and polyethylene terephthalate is preferable.
[0027] On the other hand, the copolymer polyester is preferably a polycondensation polymer of a dicarboxylic acid component and an aliphatic diol. The dicarboxylic acid component is preferably one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, and oxycarboxylic acid (e.g., p-oxybenzoic acid, etc.). The aliphatic diol is preferably one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, and neopentyl glycol. The copolymer polyester more preferably contains terephthalic acid as the dicarboxylic acid component and ethylene glycol as the aliphatic diol. When the polyester is a copolymer polyester, it is preferable that the polyester is a copolymer containing 30 mol % or less of a third component. The third component is a component other than the compound that is the main component (i.e., the component with the largest content) of the dicarboxylic acid component constituting the polyester and the compound that is the main component of the diol component, and for example, in the case of copolymerized polyethylene terephthalate, it is a component other than terephthalic acid and ethylene glycol. The copolymer polyester may also contain a structural unit derived from a difunctional compound other than a dicarboxylic acid component and an aliphatic diol. The structural unit derived from a difunctional compound other than a dicarboxylic acid component and an aliphatic diol is preferably 20 mol% or less, more preferably 10 mol% or less, based on the total moles of all structural units constituting the polyester. Examples of the bifunctional compound include various hydroxycarboxylic acids and aromatic diols.
[0028] The content of terephthalic acid in all dicarboxylic acid components constituting the present polyester film is preferably 50 mol % or more, more preferably 70 mol % or more, and further preferably 90 mol % or more. The content of ethylene glycol in all diol components constituting the present polyester film is preferably 50 mol % or more, more preferably 70 mol % or more, and further preferably 90 mol % or more. The upper limit of the content of terephthalic acid and ethylene glycol is 100 mol %.
[0029] The polyester may be a recycled polyester or a biomass-derived polyester.
[0030] <Polycondensation catalyst> The polycondensation catalyst used in polycondensing the polyester is not particularly limited, and any conventionally known compound can be used. Examples of the polycondensation catalyst include titanium compounds, germanium compounds, antimony compounds, manganese compounds, aluminum compounds, magnesium compounds, and calcium compounds. Among these, at least one of titanium compounds and antimony compounds is preferred, and it is particularly preferred to use a polyester obtained by using a titanium compound. Therefore, the present polyester film preferably contains at least one of a titanium compound and an antimony compound, and more preferably contains a titanium compound.
[0031] By using the titanium compound, the amount of antimony compound used can be reduced, which reduces the risk of new protrusions being formed due to the antimony compound precipitating on the film surface, and allows a high level of surface smoothness to be maintained. Therefore, in a particularly preferred embodiment, when the present polyester film has a multi-layer structure, the titanium compound is used for the polyester constituting at least one of the surface layers.
[0032] The titanium element content derived from the titanium compound in the surface layer is preferably 3 ppm to 40 ppm, more preferably 4 ppm to 35 ppm, based on mass. When the surface layer contains at least one of an antimony compound and a titanium compound, the antimony element content in the surface layer is preferably 0 ppm to 100 ppm. Within this range, it is possible to reduce the amount of foreign matter caused by the catalyst without reducing the production efficiency. From the viewpoint of productivity and cost, it is also preferable that the polyester constituting the layers other than the surface layer does not contain a titanium compound. As described above, by including a titanium compound in the polyester film, it is possible to obtain a polyester film having excellent smoothness. In addition, when the polyester film is made into a laminated polyester film having the resin layer, the laminated polyester film can be suitably used for forming a sheet or the like.
[0033] <Intrinsic viscosity> The intrinsic viscosity (IV) of the polyester constituting the present polyester film is preferably 0.5 dL / g or more, more preferably 0.55 dL / g or more, and even more preferably 0.6 dL / g or more. If it is within such a range, there is an advantage that the particles are highly dispersed by increasing the shear stress during kneading. In addition, the intrinsic viscosity (IV) of the polyester is, for example, 1 dL / g or less, preferably 0.8 dL / g or less, and more preferably 0.7 dL / g or less. In addition, when two or more polyesters with different intrinsic viscosities (IV) are used, the "intrinsic viscosity (IV) of the polyester constituting the present polyester film" means the intrinsic viscosity (IV) of the mixed polyesters.
[0034] When the present polyester film has a multi-layer structure, it is preferable that the intrinsic viscosity (IV) of the polyester constituting the surface layer is within the above range.
[0035] <Particle> The polyester film may contain particles, which imparts slipperiness to the polyester film and prevents scratches during each process, improving the handling properties. The type of particles contained in the polyester film is not particularly limited as long as it is a particle capable of imparting slipperiness, and specific examples include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, as well as crosslinked polymers such as crosslinked silicone resin particles, crosslinked acrylic resin particles, crosslinked styrene-acrylic resin particles, and crosslinked polyester particles, and organic particles such as calcium oxalate and ion exchange resin. Among these, organic particles, silica, aluminum oxide, and the like are preferred. Among these, it is preferred to include aluminum oxide from the viewpoint of hardening the layer to prevent the film surface from being scratched and maintaining smoothness. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst during the polyester production process can also be used.
[0036] The shape of the particles to be used is not particularly limited, and any of spherical, block, rod-like, flat, etc. may be used. There is also no particular limitation on the hardness, specific gravity, color, etc. Two or more kinds of these particles may be used in combination as necessary.
[0037] The average particle size of the particles used is usually 5 μm or less, preferably 0.01 to 3 μm, more preferably 0.02 to 1 μm, and even more preferably 0.03 to 0.5 μm. If the average particle size is 5 μm or less, the surface roughness of the film does not become too rough, and problems are unlikely to occur when forming a resin layer and various surface functional layers other than the resin layer in a later process, and this is preferable. If the average particle size is in this range, the haze is kept low, and the transparency of the laminated polyester film as a whole is easily ensured. The average particle size of particles can be determined by measuring the diameters of 10 or more particles using a scanning electron microscope (SEM) and averaging the diameters. In the case of non-spherical particles, the average of the longest and shortest diameters can be measured as the diameter of each particle.
[0038] When particles are incorporated into the polyester film, it is preferable to incorporate particles into the surface layer, for example, by providing a surface layer and an intermediate layer. In addition, when the front and back layers are differently designed, such as a three-type three-layer structure, it is also possible to incorporate particles into at least one of the surface layers. The content of particles depends on the average particle size, but is usually 5000 ppm or less, preferably 3000 ppm or less, more preferably 1000 ppm or less, based on mass in the layer containing particles. When no particles are contained or when the content of particles is small, the transparency of the polyester film is high, but the slipperiness may be insufficient. Therefore, it is necessary to improve the slipperiness by laminating the present resin layer described later. In addition, if it is 5000 ppm or less, the transparency of the polyester film can be sufficiently guaranteed. In addition, in the layer containing particles, the lower limit of the content of particles is not particularly limited, and is, for example, 50 ppm or more, preferably 100 ppm or more.
[0039] The resin layer described later may be provided on a layer of the polyester film containing particles, or may be provided on a layer that does not substantially contain particles. In addition, the surface (opposite surface) of the polyester film opposite to the surface on which the resin layer is provided may be a layer that does not substantially contain particles, or may be a layer that contains particles. In the present invention, even if both the surface on which the resin layer is provided and the opposite surface are layers that do not substantially contain particles, the winding properties can be improved by the resin layer having the uneven structure described later. In addition, by making one or both of the surface on which the resin layer is provided and the opposite surface into layers that contain particles, the winding properties can be further improved. In order to impart excellent smoothness to at least one surface of the present polyester film, the surface layer on the smooth side may contain particles or may be substantially free of particles, but in order to obtain a film with extremely high smoothness, it is preferable that the surface layer be substantially free of particles. Incidentally, "substantially not contained" means not intentionally contained, and specifically refers to the particle content (particle concentration) being less than 50 ppm by mass, more preferably 40 ppm or less, and even more preferably 30 ppm or less. In this case, by laminating the present resin layer on the surface layer on the smooth surface side and / or on the surface layer on the opposite side to the smooth surface, the handling properties when the film is wound into a roll can be improved. From the viewpoint of improving the handling properties while maintaining the smoothness of the film, it is preferable to make at least one side smooth and laminate the present resin layer on the opposite side.
[0040] The method of adding particles to the polyester film is not particularly limited, and any conventionally known method can be adopted. For example, in the case of a multi-layer polyester film, the particles can be added at any stage of the production of the polyester constituting each layer, but it is preferable to add the particles after the completion of the esterification or transesterification reaction.
[0041] <Other> In order to suppress the amount of precipitation of oligomer components, the film may be produced using a polyester having a low content of oligomer components as the raw material. As a method for producing a polyester having a low content of oligomer components, various known methods can be used, such as a method of performing solid phase polymerization after the production of a polyester. The amount of precipitation of oligomer components may be suppressed by forming the present polyester film into a three or more layer structure and forming a surface layer of the present polyester film using a polyester raw material having a low content of oligomer components. The polyester may also be obtained by carrying out the esterification or transesterification reaction, followed by melt polycondensation at a higher reaction temperature under reduced pressure.
[0042] In addition to the above-mentioned particles, conventionally known ultraviolet absorbents, antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, etc. may be added to the polyester film, if necessary.
[0043] The thickness of the polyester film is not particularly limited as long as it is within a range that allows the film to be formed, but from the viewpoints of mechanical strength, handleability, productivity, etc., the thickness is preferably 1 μm or more, more preferably 10 μm or more, even more preferably 19 μm or more, particularly preferably 25 μm or more, and is preferably 200 μm or less, more preferably 125 μm or less, even more preferably 80 μm or less, particularly preferably 50 μm or less.
[0044] <Production method of polyester film> Next, a production example of the present polyester film will be specifically described, but the production example is not limited to the following production example. For example, when producing a biaxially stretched film, a method is preferred in which the dried pellets of the polyester raw material described above are extruded as a molten sheet from a die using a melt extrusion device such as an extruder, and cooled and solidified with a cooling roll such as a rotating cooling drum to obtain an unstretched sheet. In this case, it is preferable to increase the adhesion between the sheet and the cooling roll in order to improve the flatness of the sheet, and an electrostatic application adhesion method and / or a liquid application adhesion method are preferably used.
[0045] Next, the obtained unstretched sheet is stretched in biaxial directions. In this case, the unstretched sheet is first stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 120°C, preferably 80 to 110°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3 to 6 times. Then, the film is stretched in a direction perpendicular to the first-stage stretching direction. In this case, the stretching temperature is usually 70 to 170° C., and the stretch ratio is usually 3 to 7 times, preferably 3.5 to 6 times. Then, the film is heat-treated under tension or relaxation of 30% or less at a temperature of 180 to 270° C. to obtain a biaxially stretched film. This heat treatment is also called a heat setting step. The heat treatment may be performed in two or more steps with different temperatures. After the heat treatment, the film may be cooled in a cooling zone. The cooling temperature is preferably higher than the glass transition temperature (Tg) of the polyester constituting the film, and more specifically, is preferably in the range of 100 to 160° C. This cooling may be performed in two or more steps at different temperatures. In the above stretching, a method of stretching in one direction in two or more stages can be adopted. In that case, it is preferable to perform the stretching so that the final stretch ratios in both directions are each within the above range.
[0046] The polyester film can also be produced by a simultaneous biaxial stretching method, which involves simultaneously stretching and orienting the unstretched sheet in the machine direction (longitudinal direction) and width direction (transverse direction) under a temperature controlled condition usually at 70 to 120° C., preferably 80 to 110° C., and the stretching ratio is preferably 4 to 50 times, more preferably 7 to 35 times, and even more preferably 10 to 25 times in terms of area ratio. Then, the film is subsequently heat-treated under tension or under relaxation of 30% or less at a temperature of 170 to 250° C. to obtain a stretched and oriented film. Regarding the simultaneous biaxial stretching device employing the above-mentioned stretching method, a conventionally known stretching method such as a screw method, a pantograph method, or a linear drive method can be employed.
[0047] <<Resin layer>> The laminated polyester film of the present invention comprises a resin layer formed from a resin composition on at least one side of a polyester film. The resin layer may be a cured resin layer. As described above, the present resin layer is formed from a resin composition (hereinafter also referred to as "the present composition"), and preferably has an uneven structure.
[0048] <Uneven structure> The surface structure of the present resin layer is preferably a fine uneven structure. The shape of the uneven structure may be an uneven shape and / or a mesh shape. The uneven shape is a surface uneven structure formed by fine protrusions formed by particles described later. The mesh shape is a surface uneven structure formed by coating film cracks caused by intentionally making the resin composition poor in stretchability and forming a film with poor stretchability. The mesh shape and the uneven shape may be mixed on the resin layer surface. The structure can be confirmed by various surface analysis techniques, such as an atomic force microscope (scanning probe microscope).
[0049] <Resin composition> The laminated polyester film of the present invention has a resin layer made of a resin composition, and the resin layer contains particles, that is, the resin composition contains particles. By including particles in the resin composition, the stretchability of the coating film is reduced, and the uneven structure is easily formed. In addition, the hardness of the uneven structure thus formed is increased, which makes it possible to effectively improve the air release property.
[0050] Examples of the particles include inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, zirconium oxide, aluminum oxide, and titanium oxide, as well as crosslinked polymers such as crosslinked silicone resin particles, crosslinked acrylic resin particles, crosslinked styrene-acrylic resin particles, and crosslinked polyester particles, and organic particles such as calcium oxalate and ion exchange resin. Among these, zirconium oxide, titanium oxide, and silica are preferred, and zirconium oxide and silica are more preferred. The particles may be used alone or in combination of two or more kinds.
[0051] The shape of the particles used may be spherical, blocky, rod-like, flat, chain-like, etc. Among these, spherical is preferred from the viewpoint of facilitating uniform distribution in the resin composition.
[0052] The average particle size of the particles is preferably 0.5 to 300 nm, more preferably 1 to 250 nm, even more preferably 2 to 200 nm, even more preferably 2.5 to 200 nm, even more preferably 3 to 150 nm, even more preferably 3.5 to 100 nm, even more preferably 4 to 60 nm, and particularly preferably 4.5 to 30 nm. When the average particle size is within this range, the generation of coarse protrusions due to particle aggregation and process contamination due to particle dropout can be suppressed, making it easier to obtain the desired fine uneven structure. The average particle size can be measured by a method that is more suitable for the average particle size, including a method of calculating the particle size from the specific surface area measured by a specific surface area measuring device and the particle density, a method of observing the particle with a transmission electron microscope (TEM) or scanning electron microscope (SEM) and calculating the particle diameter, and a method of determining the particle size by dynamic light scattering measurement.
[0053] The content of particles in the resin layer of the laminated polyester film is preferably 10% by mass or more. That is, the content of particles in the composition is preferably 10% by mass or more as a ratio of the total non-volatile components in the composition. The content of particles is preferably 90% by mass or less, more preferably 20 to 75% by mass, even more preferably 30 to 65% by mass, and even more preferably 35 to 60% by mass. By making the content equal to or more than the lower limit, it becomes easy to form a concave-convex structure, and the hardness of the formed concave-convex structure increases, making it easy to effectively improve air escape properties. In addition, by making the content equal to or less than 90% by mass, other components can be contained in necessary amounts, and it is possible to form a concave-convex film and obtain adhesion to the polyester film. In addition, by making the content of particles equal to or less than a certain value, it becomes easy to prevent the particles from falling off the coating film.
[0054] The present resin composition preferably contains the following components (A) and / or (B). (A) Binder resin (B) Crosslinking agent
[0055] The resin composition has low stretchability due to the above composition, and is prone to forming a fine uneven structure due to coating film cracking, which will be described later. The total content of components (A) and (B) contained in the resin composition is preferably 80% by mass or more as non-volatile components. More preferably, it is 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. If the total content is within this range, it is easy to obtain a desired fine uneven structure. The upper limit of the total content is not particularly limited, and it is sufficient if it is 100% by mass or less.
[0056] ((Component (A))) The present resin composition preferably contains a binder resin as component (A).
[0057] (binder resin) The binder resin selected as component (A) is a polymer compound having a number average molecular weight (Mn) of 1000 or more as measured by gel permeation chromatography (GPC) in accordance with the "Flow Scheme for the Safety Evaluation of Polymer Compounds" (November 1985, sponsored by the Chemical Substances Council). Among these, those having film-forming properties are preferred. Such a binder resin (A) is not particularly limited, and for example, a conventionally known binder resin such as a polyester resin, a polyurethane resin, a (meth)acrylic resin, a polyvinyl resin (polyvinyl alcohol, vinyl chloride vinyl acetate copolymer, etc.), a polyalkylene glycol, a polyalkyleneimine, methyl cellulose, hydroxy cellulose, starch, etc. can be used. Among them, from the viewpoint of film-forming property and adhesion to a polyester film, it is preferable to include one or more selected from the group consisting of a polyester resin, a polyurethane resin, and a (meth)acrylic resin, and it is more preferable to include one or more selected from the group consisting of a polyester resin and a polyurethane resin. In the present resin composition, the binder resin (A) may be used alone or in combination of two or more.
[0058] By including the binder resin (A) in the present resin composition, it becomes possible to form a film (resin layer) that holds and fixes the particles.
[0059] (polyester resin) The polyester resin may be composed of, as main components, for example, the following polyvalent carboxylic acids and polyvalent hydroxy compounds. That is, examples of polyvalent carboxylic acids that can be used include terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof. Examples of polyhydric hydroxy compounds include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. One or more of these compounds may be appropriately selected from each of them, and a polyester resin may be synthesized by a conventional polycondensation reaction.
[0060] As a part of the polycarboxylic acid, a product obtained by copolymerizing sulfoisophthalic acids such as 5-sodium sulfoisophthalic acid, introducing sulfonic acid groups into the polyester skeleton, and neutralizing the resulting product to make it hydrophilic is preferably used. The amount of copolymerization is usually 1 to 13 mol %, preferably 3 to 10 mol %, and more preferably 4 to 9 mol % based on the total amount of polycarboxylic acid. By introducing an appropriate amount of sulfonic acid groups, the hydrophilicity of the resin can be increased, and the uneven structure can be easily formed. Furthermore, the water dispersion stability can be improved.
[0061] (Polyurethane resin) The polyurethane resin is a polymeric compound having a urethane bond in the molecule, and is preferably water-dispersible or water-soluble. In the present invention, the polyurethane resin may be used alone or in combination of two or more kinds.
[0062] In order to impart water dispersibility or water solubility, it is common and preferable to introduce hydrophilic groups such as hydroxyl groups, carboxyl groups, sulfonic acid groups, sulfonyl groups, phosphoric acid groups, and ether groups into the polyurethane resin. Among the hydrophilic groups, carboxyl groups and sulfonic acid groups are particularly preferable from the viewpoint of adhesion between the resin layer and the polyester film. For example, the introduction of carboxyl groups can be carried out using carboxyl group-containing polyhydric alcohols such as dimethylolpropionic acid and dimethylolbutanoic acid.
[0063] One of the methods for preparing polyurethane resin is by the reaction of a hydroxyl group-containing compound with an isocyanate. As the hydroxyl group-containing compound used as a raw material, polyol is preferably used, for example, polyester polyols, polyether polyols, polycarbonate polyols, polyolefin polyols, and acrylic polyols. Among these, polyester polyols are preferred from the viewpoint of excellent adhesion to polyester film. These compounds may be used alone or in combination.
[0064] Examples of polyester polyols include those obtained by reacting polyvalent carboxylic acids or their acid anhydrides with polyhydric alcohols. Examples of polyvalent carboxylic acids include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, and isophthalic acid. Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 1,5-hexanediol ... ,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, lactonediols, and the like.
[0065] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.
[0066] Examples of polycarbonate-based polyols include polycarbonate diols obtained by dealcoholization reaction of polyhydric alcohols with dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, etc., such as poly(1,6-hexylene) carbonate and poly(3-methyl-1,5-pentylene) carbonate. Among the above, polyester polyols are preferred.
[0067] Examples of polyisocyanate compounds used to obtain polyurethane resins include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate; aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate. These may be used alone or in combination.
[0068] A chain extender may be used when synthesizing the polyurethane resin. The chain extender is not particularly limited as long as it has two or more active groups that react with an isocyanate group, and generally, a chain extender having two hydroxyl groups or two amino groups can be mainly used.
[0069] Examples of chain extenders having two hydroxyl groups include glycols such as aliphatic glycols, such as ethylene glycol, propylene glycol, and butanediol; aromatic glycols, such as xylylene glycol and bishydroxyethoxybenzene; and ester glycols, such as neopentyl glycol hydroxypivalate.
[0070] Examples of chain extenders having two amino groups include aromatic diamines such as tolylenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propanediamine, hexanediamine, 2,2-dimethyl-1,3-propanediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.
[0071] ((Meth)acrylic resin) The (meth)acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers. These may be homopolymers or copolymers, or copolymers with polymerizable monomers other than acrylic and methacrylic monomers. The (meth)acrylic polymer is a polymer having a structural unit derived from (meth)acrylic acid or (meth)acrylic acid alkyl esters. The (meth)acrylic polymer may be at least one polymer selected from (meth)acrylic acid and (meth)acrylic acid alkyl esters, or may be a copolymer of at least one selected from these and at least one monomer other than these, such as styrene or a styrene derivative, or a monomer containing a hydroxyl group. Also included are copolymers of these polymers with other polymers (such as polyesters and polyurethanes). For example, block copolymers and graft copolymers. That is, the (meth)acrylic resin may be a (meth)acrylic-modified polyester resin or a (meth)acrylic-modified polyurethane resin. Alternatively, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyester solution or polyester dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in a polyurethane solution or polyurethane dispersion. Similarly, it also includes a polymer (or a mixture of polymers in some cases) obtained by polymerizing a polymerizable monomer in another polymer solution or dispersion, and these are also referred to as (meth)acrylic modified polyester resins and (meth)acrylic modified polyurethane resins in this specification. The above-mentioned polyesters and polyurethanes used in the (meth)acrylic resins can be appropriately selected from those exemplified as polyesters and polyurethanes used in the binder resins described later. The (meth)acrylic resin may also contain a hydroxy group or an amino group in order to further improve adhesion to the polyester film.
[0072] The polymerizable monomer is not particularly limited, but particularly representative compounds include various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutylhydroxyfumarate, and monobutylhydroxyitaconate; and various hydroxyl group-containing monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and lauryl (meth)acrylate. Examples of such monomers include various alkyl (meth)acrylic esters; various nitrogen-containing monomers such as (meth)acrylamide, diacetone acrylamide, or (meth)acrylonitrile; nitrogen-containing monomers containing a hydroxyl group such as N-methylol (meth)acrylamide; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, and vinyl toluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.
[0073] Among the above (meth)acrylic resins, polymers obtained by polymerizing polymerizable monomers including acrylic and methacrylic monomers are preferred, and it is more preferred that the polymerizable monomers include alkyl (meth)acrylic esters. In addition, the present resin composition containing a (meth)acrylic resin is preferably diluted with a solvent to prepare a coating liquid as described below, and the solvent preferably contains water as the main solvent (50 mass% or more). That is, from the viewpoint of facilitating dissolution or dispersion when the coating liquid is made water-based, the polymerizable monomer preferably has a hydrophilic group such as a hydroxyl group or a carboxyl group. Also, from the viewpoint of effectively obtaining a concave-convex structure, it is preferable that the polymerizable monomer has a hydrophilic group such as a hydroxyl group or a carboxyl group. Therefore, the acrylic resin is preferably a polymer obtained by polymerizing an alkyl (meth)acrylic acid ester and a polymerizable monomer including a hydrophilic group-containing monomer such as a monomer containing a hydroxyl group or a monomer containing a carboxyl group. The acrylic resin may also be an emulsion polymer obtained by polymerizing a polymerizable monomer in the presence of a surfactant.
[0074] (Polyvinyl alcohol) Polyvinyl alcohol is a compound having a polyvinyl alcohol moiety, and for example, conventionally known polyvinyl alcohols can be used, including modified compounds in which polyvinyl alcohol is partially acetalized or butyralized. The degree of polymerization of polyvinyl alcohol is not particularly limited, but is usually 100 or more, preferably in the range of 300 to 40,000. When the degree of polymerization is 100 or more, the water resistance of the resin layer is easily improved. In addition, the degree of saponification of polyvinyl alcohol is not particularly limited, but a polyvinyl acetate saponification product having a degree of saponification of usually 70 mol % or more, preferably in the range of 70 to 99.9 mol %, more preferably 80 to 97 mol %, and particularly preferably 86 to 95 mol % is practically used.
[0075] (Crosslinking agent) The crosslinking agent selected as the component (B) is not particularly limited, and a conventionally known crosslinking agent can be used. By using a crosslinking agent, the resin layer is easily made into a cured resin layer. Examples of the crosslinking agent include melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, and silane coupling compounds. Among them, it is preferable to contain a melamine compound from the viewpoint of increasing the strength of the coating film and improving the adhesion with the polyester film. In the present composition, the crosslinking agent may be used alone or in combination of two or more kinds.
[0076] (Melamine compounds) The melamine compound refers to a compound having a melamine skeleton in the compound, and for example, alkylolated melamine derivatives, compounds obtained by reacting an alkylolated melamine derivative with an alcohol to partially or completely etherify the same, and mixtures thereof can be used. Examples of alkylolation include methylolation, ethylolation, isopropylolation, n-butylolation, isobutyrolation, etc. Among these, methylolation is preferred from the viewpoint of reactivity. As the alcohol used in the etherification, methanol, ethanol, isopropanol, n-butanol, isobutanol, etc. are preferably used, and among these, methanol is more preferred. The melamine compound may be either a monomer or a dimer or higher polymer, or a mixture of these may be used. Furthermore, a product obtained by co-condensing melamine with urea or the like may also be used, and a catalyst may also be used in the present resin composition to increase the reactivity of the melamine compound.
[0077] (Isocyanate compounds) The isocyanate compound is a compound having an isocyanate derivative structure, typically a blocked isocyanate, which has a structure in which the isocyanate group of an isocyanate compound, which is a precursor, is protected with a blocking agent. Examples of isocyanates include aliphatic isocyanate compounds, alicyclic isocyanate compounds, and aromatic isocyanate compounds. From the viewpoint of being able to react more highly and improving the durability of the resin layer, it is more preferable that these isocyanate compounds are compounds having a plurality of isocyanate groups, i.e., polyisocyanate compounds. In addition, when using a water-based coating liquid, it is more preferable that they are blocked isocyanates.
[0078] Examples of the aliphatic polyisocyanate compound include polyisocyanate compounds derived from aliphatic diisocyanates such as tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethyl-1,6-diisocyanatohexane, and lysine diisocyanate, lysine triisocyanate, 4-isocyanatomethyl-1,8-octamethylene diisocyanate, bis(2-isocyanatoethyl)2-isocyanatoglutarate, and compounds derived from these isocyanate compounds. Among these, hexamethylene diisocyanate is preferred because of its industrial availability.
[0079] Examples of alicyclic polyisocyanate compounds include isophorone diisocyanate, (1,3-bis(isocyanatomethyl)-cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, norbornene diisocyanate, hydrogenated xylylene diisocyanate, and compounds derived from these isocyanate compounds. Among these, isophorone diisocyanate is preferred in terms of weather resistance and industrial availability.
[0080] Examples of aromatic polyisocyanate compounds include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, naphthalene diisocyanate, xylylene diisocyanate, and compounds derived from these isocyanate compounds.
[0081] Among these polyisocyanate compounds, aliphatic polyisocyanate compounds and alicyclic polyisocyanate compounds are preferred because they have excellent weather resistance. Furthermore, among the aliphatic polyisocyanate compounds, aliphatic polyisocyanate compounds derived from aliphatic diisocyanates are preferred. Among these, hexamethylene diisocyanate is particularly preferred. Furthermore, these isocyanate compounds may be used alone or in combination of two or more.
[0082] The blocked polyisocyanate compound can be synthesized by reacting the isocyanate group of a polyisocyanate compound with a blocking agent.
[0083] Examples of the blocking agent include active methylene-based, oxime-based, pyrazole-based, alcohol-based, alkylphenol-based, phenol-based, mercaptan-based, acid amide-based, acid imide-based, imidazole-based, urea-based, amine-based, imine-based, and bisulfite-based blocking agents. Among these, active methylene-based blocking agents are preferred from the viewpoint of improving the adhesion between the resin layer and the polyester film. Two or more of these blocking agents may be used in combination.
[0084] Examples of active methylene-based blocking agents include isobutanoyl acetate, n-propanoyl acetate, n-butanoyl acetate, n-pentanoyl acetate, n-hexanoyl acetate, 2-ethylheptanoyl acetate, malonic acid ester, acetoacetate, acetylacetone, etc. Among them, in terms of excellent low-temperature curing properties and storage stability in the presence of water, isobutanoyl acetate, n-propanoyl acetate, n-butanoyl acetate, n-pentanoyl acetate, n-hexanoyl acetate, and 2-ethylheptanoyl acetate are preferred, more preferably isobutanoyl acetate, n-propanoyl acetate, and n-pentanoyl acetate, and even more preferably isobutanoyl acetate. More specifically, examples of isobutanoyl acetate include methyl isobutanoyl acetate, ethyl isobutanoyl acetate, n-propyl isobutanoyl acetate, isopropyl isobutanoyl acetate, n-butyl isobutanoyl acetate, isobutyl isobutanoyl acetate, t-butyl isobutanoyl acetate, n-pentyl isobutanoyl acetate, n-hexyl isobutanoyl acetate, 2-ethylhexyl isobutanoyl acetate, phenyl isobutanoyl acetate, and benzyl isobutanoyl acetate. Among these, methyl isobutanoyl acetate and ethyl isobutanoyl acetate are preferred. Examples of n-propanoyl acetate include methyl n-propanoyl acetate, ethyl n-propanoyl acetate, isopropyl n-propanoyl acetate, n-butyl n-propanoyl acetate, and t-butyl n-propanoyl acetate. Among these, methyl n-propanoyl acetate and ethyl n-propanoyl acetate are preferred. Examples of n-pentanoyl acetate include methyl n-pentanoyl acetate, ethyl n-pentanoyl acetate, isopropyl n-pentanoyl acetate, n-butyl n-pentanoyl acetate, t-butyl n-pentanoyl acetate, etc. Among these, methyl n-pentanoyl acetate and ethyl n-pentanoyl acetate are preferred.
[0085] In the active methylene blocked isocyanate compound used in the present invention, the active methylene blocking agent shown above can be used alone or in combination of two or more. As the active methylene blocking agent to be used in combination, dimethyl malonate and diethyl malonate are preferred in terms of excellent low-temperature curing properties and excellent durability of the formed resin layer.
[0086] Examples of oxime-based blocking agents include formaldoxime, acetaldoxime, acetoneoxime, methylethylketoxime, cyclohexanoneoxime, etc. Examples of pyrazole-based blocking agents include pyrazole, 3-methylpyrazole, 3,5-dimethylpyrazole, etc. Examples of alcohol-based blocking agents include methanol, ethanol, 2-propanol, n-butanol, sec-butanol, 2-ethyl-1-hexanol, 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, etc. Examples of alkylphenol-based blocking agents include monoalkylphenols such as n-propylphenol, isopropylphenol, n-butylphenol, sec-butylphenol, t-butylphenol, n-hexylphenol, 2-ethylhexylphenol, n-octylphenol, and n-nonylphenol, and dialkylphenols such as di-n-propylphenol, diisopropylphenol, isopropylcresol, di-n-butylphenol, di-t-butylphenol, di-sec-butylphenol, di-n-octylphenol, di-2-ethylhexylphenol, and di-n-nonylphenol. Examples of phenol-based blocking agents include phenol, cresol, ethylphenol, styrenated phenol, and hydroxybenzoic acid ester. Examples of mercaptan-based blocking agents include butyl mercaptan and dodecyl mercaptan. Examples of acid amide-based blocking agents include acetanilide, acetic acid amide, ε-caprolactam, δ-valerolactam, and γ-butyrolactam. Examples of the acid imide-based blocking agent include succinimide and maleimide. Examples of the imidazole-based blocking agent include imidazole and 2-methylimidazole. Examples of the urea-based blocking agent include urea, thiourea, and ethyleneurea. Examples of the amine-based blocking agent include diphenylamine, aniline, carbazole, di-n-propylamine, diisopropylamine, and isopropylethylamine. Examples of the imine-based blocking agent include ethyleneimine and polyethyleneimine.
[0087] The blocked isocyanate compound used in the present invention preferably contains a hydrophilic moiety in order to improve its compatibility with aqueous paints. Examples of a method for adding a hydrophilic moiety to a blocked isocyanate compound include a method of reacting an isocyanate group of an isocyanate compound, which is a precursor, with a hydrophilic compound having active hydrogen.
[0088] Examples of hydrophilic compounds having active hydrogen that are used in the blocked isocyanate compound used in the present invention include polyethylene glycol compounds, carboxylic acid group-containing compounds, sulfonic acid group-containing compounds, amine-containing compounds, etc. These hydrophilic compounds may be used alone or in combination of two or more kinds.
[0089] Examples of polyethylene glycol compounds include monoalkoxypolyethylene glycol, polyethylene glycol, polyoxypropylene polyoxyethylene copolymer diol, polyoxypropylene polyoxyethylene block polymer diol, and the like. Among these, monoalkoxypolyethylene glycols such as monomethoxypolyethylene glycol and monoethoxypolyethylene glycol are particularly preferred.
[0090] The carboxylic acid group-containing compound includes monohydroxycarboxylic acids, dihydroxycarboxylic acids, derivatives thereof, etc. Among the carboxylic acid group-containing compounds, monohydroxycarboxylic acids and dihydroxycarboxylic acids are preferred, and monohydroxycarboxylic acids are more preferred.
[0091] Specific examples of the carboxylic acid group-containing compound include hydroxypivalic acid, 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and derivatives such as polycaprolactone diol and polyether polyol using these as initiators, and salts thereof.
[0092] Examples of sulfonic acid group-containing compounds include aminoethylsulfonic acid, ethylenediamino-propyl-β-ethylsulfonic acid, 1,3-propylenediamine-β-ethylsulfonic acid, N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid, and salts thereof.
[0093] Examples of the amine-containing compound include hydroxyl-containing amino compounds, such as dimethylethanolamine and diethylethanolamine.
[0094] (Oxazoline compounds) The oxazoline compound is a compound having an oxazoline group in the molecule, and in particular, a polymer containing an oxazoline group is preferred, and can be prepared by polymerization of an addition polymerizable oxazoline group-containing monomer alone or with other monomers. Examples of the addition polymerizable oxazoline group-containing monomer include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline, and one or a mixture of two or more of these can be used. Among these, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially. The other monomer is not limited as long as it is a monomer that can be copolymerized with the addition-polymerizable oxazoline group-containing monomer, and examples thereof include (meth)acrylic acid esters such as alkyl (meth)acrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, and cyclohexyl groups); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid, and salts thereof (sodium salts, potassium salts, ammonium salts, tertiary amine salts, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl (meth)acrylate, etc. Examples of the monomer include unsaturated amides such as t)acrylamide and N,N-dialkyl(meth)acrylamide (the alkyl group can be a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a 2-ethylhexyl group, a cyclohexyl group, and the like); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride and vinylidene chloride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. One or more of these monomers can be used. The oxazoline compound may have a polyalkylene oxide chain such as a polyethylene oxide chain, and for example, a (meth)acrylate having a polyalkylene oxide chain may be used as another monomer. From the viewpoint of improving the adhesion of the resin layer to the polyester film, the amount of oxazoline groups in the oxazoline compound is preferably in the range of 0.5 to 10 mmol / g, more preferably 1 to 9 mmol / g, and further preferably 3 to 8 mmol / g.
[0095] (Epoxy compounds) The epoxy compound is a compound having an epoxy group in the molecule, and examples thereof include condensations of epichlorohydrin, ethylene glycol, polyethylene glycol, glycerin, polyglycerin, bisphenol A, etc. with a hydroxyl group or an amino group, polyepoxy compounds, diepoxy compounds, monoepoxy compounds, and glycidylamine compounds. Examples of the polyepoxy compound include sorbitol polyglycidyl ether, polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether. Examples of diepoxy compounds include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Examples of the monoepoxy compound include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether, and examples of the glycidylamine compound include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylamino)cyclohexane, etc. From the viewpoint of improving the adhesion of the resin layer to the polyester film, polyether-based epoxy compounds are preferred. In terms of the amount of epoxy groups, a polyepoxy compound having three or more functional groups is more preferable than a difunctional compound.
[0096] (Carbodiimide compounds) A carbodiimide compound is a compound having a carbodiimide structure, i.e., a compound having one or more carbodiimide structures in its molecule. However, for better adhesion between the resin layer and the polyester film, a polycarbodiimide compound having two or more carbodiimide structures in its molecule is more preferred.
[0097] Carbodiimide compounds can be synthesized by conventionally known techniques, and generally, condensation reaction of diisocyanate compounds is used. The diisocyanate compounds are not particularly limited, and both aromatic and aliphatic compounds can be used, and specific examples include tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate. Furthermore, within the scope of the present invention, in order to improve the water solubility or water dispersibility of the polycarbodiimide compound, a surfactant may be added, or a hydrophilic monomer such as a polyalkylene oxide, a quaternary ammonium salt of a dialkylamino alcohol, or a hydroxyalkylsulfonate may be added.
[0098] (Silane coupling compound) A silane coupling compound is an organosilicon compound that has an organic functional group and a hydrolyzable group such as an alkoxy group in one molecule. For example, epoxy group-containing compounds such as 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; vinyl group-containing compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; styryl group-containing compounds such as p-styryltrimethoxysilane and p-styryltriethoxysilane; (meth)acrylic group-containing compounds such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3 -aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane and other amino group-containing compounds; tris(trimethoxysilylpropyl)isocyanurate, tris(triethoxysilylpropyl)isocyanurate and other isocyanurate group-containing compounds; 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane and other mercapto group-containing compounds.
[0099] The content of component (A) in the composition is preferably 5 to 95% by mass, more preferably 10 to 80% by mass, even more preferably 20 to 70% by mass, and even more preferably 30 to 60% by mass, as a percentage of the total non-volatile components in the composition. By making the content equal to or greater than the lower limit, a film having film-forming properties and containing particles can be obtained. In addition, the film has adhesion to the polyester film, and thus the falling off of the coating film can be suppressed. In addition, by making the content equal to or less than the upper limit, a high particle content is obtained, and the coating film hardness is increased, making it possible to form unevenness in the coating film. The content of component (B) in the present resin composition is preferably 5 to 50 mass%, more preferably 8 to 40 mass%, further preferably 10 to 35 mass%, and particularly preferably 15 to 30 mass%, as a ratio of the total non-volatile components in the present resin composition. By making the content equal to or greater than the lower limit, a film having film-forming properties and containing particles can be obtained. In addition, by making the content equal to or less than the upper limit, a high particle content is obtained, and the hardness of the coating film can be increased, thereby making it possible to form unevenness in the coating film.
[0100] Incidentally, film-forming properties can be obtained by using a binder resin as component (A), but from the viewpoint of further improving the coating film strength and adhesion to the polyester film, it is more preferable to use a crosslinking agent in combination with the binder resin.
[0101] (Other ingredients) In addition to the above-mentioned components, additives such as crosslinking catalysts, defoamers, coatability improvers, surfactants, thickeners, organic lubricants, ultraviolet absorbers, antioxidants, foaming agents, dyes, and pigments may be appropriately added within the scope of the present invention.
[0102] (solvent) The present resin composition may be diluted with a solvent to form a coating liquid, that is, the present resin composition may be applied as a liquid coating liquid to, for example, the present polyester film, and then dried and cured as necessary to form a resin layer. Each of the components constituting the present resin composition (components (A) and (B) and other components, etc.) may be dissolved or dispersed in a solvent. When the composition is used as a coating solution, the concentration of the total non-volatile components of the resin composition in the coating solution is preferably 0.1 to 50% by mass. If the concentration is equal to or higher than the lower limit, a resin layer of a desired thickness can be efficiently formed. On the other hand, if the concentration is equal to or lower than the upper limit, the viscosity during coating can be suppressed, thereby improving the appearance of the resin layer and increasing the stability in the coating solution.
[0103] The solvent is not particularly limited, and either water or an organic solvent can be used. From the viewpoint of environmental protection, it is preferable to prepare an aqueous coating liquid using water as the main solvent (50% by mass or more of the total solvent). The water content is preferably 60% by mass or more, more preferably 70% by mass or more. The aqueous coating liquid may contain a small amount of an organic solvent. The specific amount of the organic solvent is preferably equal to or less than the amount of water on a mass basis, for example, 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less of the solvent. Examples of organic solvents used in combination with water include alcohols such as ethanol, isopropanol, ethylene glycol, and glycerin; ethers such as ethyl cellosolve, t-butyl cellosolve, propylene glycol monomethyl ether, and tetrahydrofuran; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate; and amines such as dimethylethanolamine. These can be used alone or in combination. By appropriately selecting and adding these organic solvents to the aqueous coating liquid as necessary, the stability and coatability of the coating liquid may be improved.
[0104] In addition, when only an organic solvent is used as the solvent, examples of such an organic solvent include aromatic hydrocarbons such as toluene, aliphatic hydrocarbons such as hexane, heptane, isooctane, esters such as ethyl acetate, butyl acetate, ketones such as ethyl methyl ketone, isobutyl methyl ketone, alcohols such as ethanol, 2-propanol, ethers such as diisopropyl ether, dibutyl ether, etc. These may be used alone or in combination, taking into consideration solubility, coatability, boiling point, etc.
[0105] It can be assumed that the resin layer contains unreacted components of the resin composition (components (A) and (B) and other components, etc.), reacted compounds, or a mixture of these. The components in the resin layer can be analyzed by, for example, TOF-SIMS, ESCA, fluorescent X-rays, or the like.
[0106] <Method of forming resin layer> Next, a method for forming the resin layer constituting the present laminated polyester film will be described. The present resin layer may be formed by applying the present resin composition to a polyester film and, if necessary, subjecting the applied resin composition to treatments such as drying, curing, heat treatment, etc., and it is preferable to at least perform heat treatment. The method for applying the resin composition is not particularly limited, and any conventionally known coating method such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, etc. can be used.
[0107] The resin layer can be formed by in-line coating or off-line coating. The method of heat-treating the applied resin composition is not particularly limited, and when the resin layer is formed by off-line coating, the heat treatment is usually performed at 80 to 200°C for 3 to 40 seconds, preferably at 100 to 180°C for 3 to 40 seconds. On the other hand, when the resin layer is formed by in-line coating, the heat treatment is usually performed at 70 to 280°C for 3 to 200 seconds. The heat treatment may be performed in two or more steps at different temperatures within the above temperature range. At least a part of the heat treatment may be performed by heating during stretching. Drying and curing may be performed together by heating in the heat treatment.
[0108] In the present invention, the resin layer is preferably formed by in-line coating, which is a method for treating the surface of a polyester film during the film-forming process. In-line coating is a method of coating within the polyester film production process, specifically, coating at any stage from melt extrusion of polyester to stretching, heat setting and winding up. Usually, coating is performed on any of the following: an unstretched sheet obtained by melting and quenching, a stretched uniaxially stretched film, a biaxially stretched film before heat setting, or a film after heat setting and before winding up.
[0109] Although not limited to the following, for example, in the case of sequential biaxial stretching, a method in which a uniaxially stretched film stretched in the longitudinal direction (machine direction) is coated and then stretched in the transverse direction is particularly advantageous. According to such a method, film formation and resin layer formation can be carried out simultaneously, which is advantageous in terms of production costs, and since stretching is carried out after coating, the thickness of the resin layer can be changed by the stretching ratio, and thin film coating can be carried out more easily than with off-line coating films.
[0110] Furthermore, by providing a resin layer on the film before stretching, the resin layer can be stretched together with the polyester film, and this allows the resin layer to be firmly attached to the polyester film.
[0111] Furthermore, in the production of biaxially stretched polyester film, the film can be stretched while holding the ends with clips or the like, thereby restraining the film in both the vertical and horizontal directions. This allows the film to be subjected to high temperatures in the subsequent heat treatment (heat fixing process) without wrinkles or the like being formed and while maintaining its flatness. Therefore, the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, so that the film-forming property of the resin layer is improved and the resin layer and the polyester film can be more firmly adhered to each other. Furthermore, a strong resin layer can be formed, and the performance such as migration resistance and moist heat resistance of various functional layers that can be formed on the resin layer can be improved.
[0112] In particular, in the present invention, this method is optimal as a manufacturing method for forming coating film cracks. The contents of the particles in the resin composition and the components (A) and (B) blended as necessary are appropriately adjusted to intentionally make the resin composition poor in stretchability. In this way, a manufacturing method is adopted in which the resin composition is coated and then stretched. That is, coating film cracks caused by stretching a film with poor stretchability make it easy to form an uneven structure on the resin layer surface. Those skilled in the art have traditionally considered coating film cracks to be one form of coating defect, and have required uniform coating film formation that minimizes the occurrence of coating film cracks. One cause of coating film cracks is insufficient stretchability of the resin composition, so the resin composition is designed to have sufficient stretchability. However, the present inventors have come to use such coating film cracks as one of the means for forming a fine surface structure on the resin layer surface.
[0113] Regardless of whether off-line coating or in-line coating is used, heat treatment and irradiation with active energy rays such as ultraviolet rays may be used in combination as necessary. The polyester film constituting the present laminated polyester film may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.
[0114] The coating amount of the non-volatile component of the present resin layer is preferably 0.005 to 0.95 g / m 2 , more preferably 0.02 to 0.5 g / m 2 , and more preferably 0.04 to 0.3 g / m 2 , and particularly preferably 0.06 to 0.2 g / m 2If the coating amount is within this range, a fine uneven structure can be formed by coating film cracking or the like. The coating amount can be calculated from the concentration of non-volatile components in the coating solution, the coating amount before drying derived from the consumption amount of the coating solution, the transverse stretching ratio, and the like. The coating amount of the non-volatile component refers to the coating amount in the present laminated polyester film, and for example, in the case where drying and stretching are performed, it refers to the coating amount after drying and stretching.
[0115] <<Release layer>> In a preferred embodiment of the present laminated polyester film, a resin layer is provided on one side of the polyester film and a release layer is provided on the opposite side. The release layer may be laminated on the polyester film directly or via another layer, such as an easy-adhesion coating layer for improving adhesion to the polyester film, an antistatic layer, an antiblocking layer, etc.
[0116] <Release Agent Composition> The present release layer is preferably formed from a release agent composition (hereinafter also referred to as "the present release agent composition"). The present release agent composition also contains a release agent.
[0117] ((Release Agent)) The release agent is not particularly limited, and a conventionally known release agent can be used. For example, silicone compounds, long-chain alkyl group-containing compounds, waxes, fluorine compounds, etc. can be mentioned. Among them, at least one of silicone compounds and long-chain alkyl group-containing compounds is preferable. In the present release agent composition, the release agent may be used alone or in combination of two or more kinds.
[0118] (Silicone compounds) Silicone compounds are compounds having a silicone structure in the molecule, in other words, compounds having a main skeleton formed by siloxane bonds. Examples of silicone compounds or main skeletons constituting silicone compounds include organopolysiloxanes such as polydimethylsiloxane, acrylic graft silicone, silicone graft acrylic, amino-modified silicone, perfluoroalkyl-modified silicone, and alkyl-modified silicone. Among them, organopolysiloxanes such as polydimethylsiloxane are preferred from the viewpoint of excellent releasability.
[0119] Among them, silicone compounds having functional groups capable of reacting with (meth)acryloyl groups in the compounds containing (meth)acryloyl groups described later are preferred, and among them, silicone compounds containing Si-H groups are particularly preferred. The Si-H groups of silicone compounds have the property of enhancing adhesion to the polyester film. Among them, silicone compounds having Si-H groups and alkenyl groups are preferred from the viewpoint of forming a crosslinked structure having a skeleton derived from silicone compounds in the release layer.
[0120] The molecular weight of the silicone compound is not particularly limited. In particular, from the viewpoint of adhesion between the polyester film and the release layer, the number average molecular weight is preferably 5000 or more, more preferably 10000 or more. The upper limit is not particularly limited, but is usually 1000000 or less. The number average molecular weight of the silicone compound can be measured, for example, by gel permeation chromatography (GPC) and calculated as a polystyrene equivalent value.
[0121] The silicone compound used in the present release agent composition preferably contains a curable silicone compound in consideration of heat resistance and staining resistance. As the type of curable silicone compound, any curing reaction type can be used, such as addition curing type, condensation curing type, ultraviolet curing type, electron beam curing type, etc. Among them, addition curing type silicone compounds are more preferred from the viewpoint of increasing the coating film cohesive strength.
[0122] An addition curing silicone compound is a silicone compound that has unsaturated hydrocarbon groups and hydrogen groups as functional groups in its structure, and the addition curing reaction occurs by the reaction of these functional groups. That is, it is a mixture of a silicone compound having a Si-H group and a silicone compound containing an alkenyl group, or a silicone compound that contains a Si-H group and a vinyl group in the molecule. From the viewpoint of pot life, it is preferable that the unsaturated hydrocarbon group and the hydrogen group are not present in the same molecule, and it is preferable to use a mixture of functional groups contained in separate silicone molecules.Therefore, it is preferable to use a mixture of a silicone compound having an unsaturated hydrocarbon group as a functional group and a silicone compound having a hydrogen group as a functional group.
[0123] An example of the silicone compound having an unsaturated hydrocarbon group as a functional group is polydimethylsiloxane containing an unsaturated hydrocarbon group. At least two unsaturated hydrocarbon groups must be contained in the polydimethylsiloxane molecule. Examples of the unsaturated hydrocarbon group include alkenyl groups having 2 to 8 carbon atoms, such as vinyl groups, propenyl groups, butenyl groups, and pentenyl groups. Among these, vinyl groups are preferred because of their industrial availability. The at least two alkenyl groups may have different numbers of carbon atoms. The polydimethylsiloxane containing an unsaturated hydrocarbon group has an alkenyl group and a methyl group as functional groups directly bonded to a silicon atom, and may also have various other functional groups. Examples of functional groups other than the methyl group include alkyl groups such as ethyl, propyl, and butyl groups, cycloalkyl groups such as cyclohexyl groups, aryl groups such as phenyl and methylphenyl groups, and alkoxy groups such as hydroxy, methoxy, and ethoxy groups. From the viewpoint of adhesion to polyester films, it is preferable to include a phenyl group or a methoxy group.
[0124] On the other hand, the silicone compound having a hydrogen group as a functional group can be exemplified by a polydimethylsiloxane containing a hydrogen group. A polydimethylsiloxane containing a hydrogen group is a polydimethylsiloxane having a hydrogen atom bonded to a silicon atom. It is necessary that one molecule contains at least two hydrogen atoms bonded to a silicon atom, and from the viewpoint of curing properties, it is preferable that one molecule contains three or more hydrogen atoms. The hydrogen atom bonded to silicon may be at the end or side chain of the polydimethylsiloxane molecular chain. Hydrogen-containing polydimethylsiloxane has hydrogen and methyl groups as functional groups directly bonded to silicon atoms, but may also have various other functional groups. Examples of functional groups other than methyl groups include alkyl groups such as ethyl, propyl, and butyl groups, cycloalkyl groups such as cyclohexyl groups, aryl groups such as phenyl and methylphenyl groups, hydroxy groups, and alkoxy groups such as methoxy and ethoxy groups.
[0125] The polydimethylsiloxane skeleton of the unsaturated hydrocarbon group-containing polydimethylsiloxane and the hydrogen group-containing polydimethylsiloxane may each be linear or branched.
[0126] The blend of the unsaturated hydrocarbon-containing polydimethylsiloxane and the hydrogen group-containing polydimethylsiloxane is preferably such that the molar ratio of the total Si-H groups to the total alkenyl groups (Si-H group amount / alkenyl group amount) is 1.0 to 5.0. When the molar ratio is 1.0 or more, curability can be maintained, and when it is 5.0 or less, the amount of remaining Si-H groups is not too large, and the peel force from the adhesive does not become too strong, which is preferable. From this viewpoint, the molar ratio is preferably 1.0 to 5.0, more preferably 1.6 or more or 4.8 or less, and even more preferably 2.0 or more or 4.6 or less.
[0127] The silicone compound used in the present release agent composition may be a solvent-curable silicone or a solventless-curable silicone. It is also possible to use a mixture of a solvent-curable silicone and a solventless-curable silicone. In addition, in both the solvent-curable silicone and the solventless-curable silicone, it is preferable that the curable silicone has releasability and includes an addition reaction between a vinyl group and a group having a silicon-hydrogen bond during the curing process (so-called addition type silicone).
[0128] From the viewpoints of the working environment and safety in terms of the risk of organic solvent explosion and fire, the above-mentioned silicone compound is preferably used in the form of a silicone emulsion. When the silicone compound is emulsified, a surfactant component can be used as an emulsion stabilizer.
[0129] The surfactant may be a nonionic surfactant or an anionic surfactant. Examples of nonionic surfactants include polyoxyalkylene alkyl ethers such as polyoxyethylene alkyl ethers, polyoxyalkylene phenyl ethers such as polyoxyethylene phenyl ethers, glycerin alkyl ethers, glycerin fatty acid esters and their alkylene glycol adducts, polyglycerin fatty acid esters and their alkylene glycol adducts, propylene glycol fatty acid esters and their alkylene glycol adducts, polyalkylene glycol fatty acid esters, etc. Examples of anionic surfactants include fatty acid soaps such as sodium stearate and triethanolamine palmitate, alkyl ether carboxylic acids and their salts, alkyl sulfonic acids, alkenyl sulfonates, sulfonates of fatty acid esters, alkyl sulfates, secondary higher alcohol sulfates, alkyl and allyl ether sulfates, fatty acid ester sulfates, polyoxyethylene alkyl sulfates, sulfates such as turpentine oil, alkyl phosphates, ether phosphates, alkyl allyl ether phosphates, amide phosphates, etc. Of these, nonionic surfactants are preferred, and from the standpoint of the stability of the silicone emulsion, polyoxyalkylene alkyl ethers and polyoxyalkylene phenyl ethers are more preferred.
[0130] Examples of polyoxyalkylene alkyl ethers include polyoxyethylene alkyl ethers, polyoxypropylene alkyl ethers, and polyoxybutylene alkyl ethers. Among these, polyoxyethylene alkyl ethers are preferred. The alkyl group is preferably a linear or branched alkyl group having 8 to 30 carbon atoms, and more preferably a linear or branched alkyl group having 8 to 16 carbon atoms.
[0131] Examples of polyoxyalkylene phenyl ether include polyoxyethylene phenyl ether, polyoxypropylene phenyl ether, and polyoxybutylene phenyl ether. Among these, polyoxyethylene phenyl ether is preferred. The phenyl group is preferably an unsubstituted or substituted phenyl group, and a styrenated phenyl group in which the hydrogen atom of the phenyl group is substituted with a styryl group is preferred.
[0132] (Long-chain alkyl group-containing compounds) The long-chain alkyl group-containing compound refers to a compound having a straight-chain or branched alkyl group having 6 or more carbon atoms, preferably 8 or more, and more preferably 12 or more carbon atoms. Examples of the alkyl group include alkyl groups having about 6 to 30 carbon atoms, such as hexyl, octyl, decyl, lauryl, octadecyl, and behenyl. Examples of compounds having an alkyl group include various long-chain alkyl group-containing polymer compounds, long-chain alkyl group-containing amine compounds, long-chain alkyl group-containing ether compounds, and long-chain alkyl group-containing quaternary ammonium salts. Considering heat resistance and staining resistance, polymer compounds are preferred. In addition, from the viewpoint of effectively obtaining releasability, polymer compounds having a long-chain alkyl group in the side chain are more preferred.
[0133] The polymer compound having a long-chain alkyl group in the side chain can be obtained by reacting a polymer having a reactive group with a compound having an alkyl group capable of reacting with the reactive group. Examples of the reactive group include hydroxyl group, amino group, carboxyl group, and acid anhydride. Examples of compounds having these reactive groups include polyvinyl alcohol, polyethyleneimine, polyethyleneamine, reactive group-containing polyester resin, and reactive group-containing poly(meth)acrylic resin. Among these, polyvinyl alcohol is preferable in consideration of releasability and ease of handling. The degree of polymerization of the polyvinyl alcohol used is not particularly limited, but is usually 100 or more, preferably in the range of 300 to 40,000. In addition, the degree of saponification of the polyvinyl alcohol is not particularly limited, but is usually 70 mol% or more, preferably in the range of 70 to 99.9 mol%, more preferably 80 to 97 mol%, and even more preferably 86 to 95 mol%.
[0134] Examples of compounds having an alkyl group capable of reacting with the reactive group include long-chain alkyl group-containing isocyanates such as hexyl isocyanate, octyl isocyanate, decyl isocyanate, lauryl isocyanate, octadecyl isocyanate, behenyl isocyanate, etc., long-chain alkyl group-containing acid chlorides such as hexanoyl chloride, octanoyl chloride, decanoyl chloride, lauroyl chloride, octadecanoyl chloride, behenoyl chloride, etc., long-chain alkyl group-containing amines, long-chain alkyl group-containing alcohols, etc. Among these, in consideration of ease of handling, long-chain alkyl group-containing isocyanates are preferred, and octadecyl isocyanate is particularly preferred.
[0135] Furthermore, polymeric compounds having a long-chain alkyl group in the side chain can also be obtained by polymerization of a long-chain alkyl (meth)acrylate or copolymerization of a long-chain alkyl (meth)acrylate with another vinyl group-containing monomer. Examples of long-chain alkyl (meth)acrylate include hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, octadecyl (meth)acrylate, and behenyl (meth)acrylate.
[0136] When a silicone compound is used as the release agent, the content of the silicone compound in the release agent composition is preferably 50 to 100% by mass, more preferably 70 to 100% by mass, even more preferably 90 to 99% by mass, and particularly preferably 95 to 99% by mass, as a ratio of the total non-volatile components in the release agent composition. If the silicone compound is contained in the release layer at the above lower limit or more, sufficient releasability can be obtained, which is preferable. In addition, by making the content the above upper limit or less, a compound containing a (meth)acryloyl group, which will be described later, can be contained, so that the adhesion to the polyester film can be further improved.
[0137] When a release agent other than a silicone compound (for example, a long-chain alkyl group-containing compound, a wax, a fluorine compound, etc.) is used as the release agent, the content of the release agent other than a silicone compound in the release agent composition is preferably 10 to 90 mass%, more preferably 20 to 80 mass%, further preferably 30 to 70 mass%, and particularly preferably 50 to 70 mass%, as a ratio of the total non-volatile components in the release agent composition. By making the content equal to or more than the above lower limit, the release property becomes good. In addition, by making the content equal to or less than the above upper limit, sufficient solvent resistance can be obtained.
[0138] ((Crosslinking Agent)) When a release agent other than a silicone compound is used as the release agent, the release agent composition preferably contains a crosslinking agent. The crosslinking agent is not particularly limited, and a conventionally known crosslinking agent can be used. By using a crosslinking agent, the strength of the release layer can be increased, and the layer can be made to be less susceptible to transfer of the release component. Examples of the crosslinking agent include a melamine compound, an oxazoline compound, an epoxy compound, a carbodiimide compound, an isocyanate compound, and a silane coupling compound. Among them, from the viewpoint of strengthening the strength of the release layer and improving the adhesion with the polyester film, it is preferable that the crosslinking agent contains a melamine compound. In the present release agent composition, the crosslinking agent may be used alone or in combination of two or more kinds. The specific and preferred aspects of the crosslinking agent that can be contained in the present release agent composition are the same as those of the crosslinking agent that can be contained in the present resin composition, and all of these can be used. In other words, the crosslinking agents exemplified in the present release agent composition are the same as those exemplified as the crosslinking agents in the present resin composition.
[0139] When the release agent composition contains a crosslinking agent, the content of the crosslinking agent in the release agent composition is preferably 10 to 90% by mass, more preferably 20 to 80% by mass, further preferably 30 to 70% by mass, and particularly preferably 30 to 50% by mass, as a ratio of the total non-volatile components in the release agent composition. By making the content equal to or greater than the lower limit, the strength of the release layer can be improved. In addition, by making the content equal to or less than the upper limit, sufficient releasability can be ensured.
[0140] ((Compound containing a (meth)acryloyl group)) When a silicone compound is used as the release agent, the release agent composition may further contain a compound containing a (meth)acryloyl group. By containing a compound containing a (meth)acryloyl group, the adhesion to the polyester film can be further improved.
[0141] The compound containing a (meth)acryloyl group may be a polymeric (meth)acrylate compound or a monomeric (meth)acrylate compound. Either of these may be used. These may also be used in combination. Here, the polymeric (meth)acrylate compound refers to a macromonomer.
[0142] Examples of the (meth)acrylate compound include urethane (meth)acrylate compounds, epoxy (meth)acrylate compounds, polyester (meth)acrylate compounds, polyalkylene (meth)acrylate compounds, other (meth)acrylate compounds, etc. Among them, the compound containing a (meth)acryloyl group is preferably a urethane (meth)acrylate, or a mixture of a urethane (meth)acrylate and a (meth)acrylate compound other than urethane (meth)acrylate.
[0143] The urethane (meth)acrylate compound may be a conventionally known compound, and is not particularly limited, but may be, for example, a compound obtained by reacting a (meth)acrylate compound having a hydroxyl group with an isocyanate compound, or a compound obtained by reacting a (meth)acrylate compound having a hydroxyl group with a polyol and an isocyanate compound. The urethane (meth)acrylate compound may be a polymer or a monomer, but is preferably a polymer from the viewpoint of adhesion to the polyester film.
[0144] Examples of the (meth)acrylate compound having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerin mono(meth)acrylate, glycerin di(meth)acrylate, diglycerin mono(meth)acrylate, diglycerin tri(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol mono(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, sorbitol di(meth)acrylate, sorbitol tri(meth)acrylate, sorbitol tetra(meth)acrylate, sorb ... tri(meth)acrylate, sorbitol tri(meth)acrylate, sorbitol tri(meth)acrylate, sorbitol tri(meth)acrylate, sorbitol tri( Examples of the reaction products include reaction products of (meth)acrylic acid and polyol diglycidyl such as (meth)acrylic acid, sorbitol mono(meth)acrylate diglycerin di(meth)acrylate, an adduct of glycidyl (meth)acrylate and (meth)acrylic acid, a reaction product of two molecules of (meth)acrylic acid and one molecule of 1,6-hexanediol diglycidyl, a reaction product of two molecules of epoxy (meth)acrylic acid and one molecule of neopentyl glycol diglycidyl, a reaction product of two molecules of (meth)acrylic acid and one molecule of bisphenol A diglycidyl, a reaction product of two molecules of (meth)acrylic acid and a diglycidyl form of a propylene oxide adduct of bisphenol A, a reaction product of two molecules of (meth)acrylic acid and one molecule of diglycidyl phthalate, a reaction product of two molecules of (meth)acrylic acid and one molecule of polyethylene glycol diglycidyl, and a reaction product of two molecules of (meth)acrylic acid and one molecule of polypropylene glycol diglycidyl. These may be used alone or in combination of two or more kinds.
[0145] Among these, from the viewpoint of more effectively improving the adhesion between the silicone compound and the polyester film, those having three or more (meth)acryloyl groups in one molecule, such as diglycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, sorbitol tri(meth)acrylate, sorbitol tetra(meth)acrylate, and sorbitol penta(meth)acrylate, are preferred, and those having five or more (meth)acryloyl groups in one molecule, such as dipentaerythritol penta(meth)acrylate and sorbitol penta(meth)acrylate, are more preferred.
[0146] The isocyanate compound is a compound having an isocyanate or an isocyanate derivative structure, typically a blocked isocyanate. Examples of the isocyanate include aromatic isocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic isocyanates having an aromatic ring such as α,α,α',α'-tetramethylxylylene diisocyanate; aliphatic isocyanates such as methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic isocyanates such as cyclohexane diisocyanate, dicyclohexylmethane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. The isocyanate may be a reaction product of these isocyanates with various polymers or compounds. In addition, polymers or derivatives such as biuretized products, isocyanurate products, uretdione products, and carbodiimide modified products of these isocyanates may be mentioned. These may be used alone or in combination of two or more kinds. Among the above isocyanates, aliphatic isocyanates or alicyclic isocyanates are preferred, and alicyclic isocyanates are more preferred, from the viewpoint of improving the adhesion of the release layer to the polyester film.
[0147] Examples of the polyol include polycarbonate polyol, polyester polyol, polyether polyol, etc., and either high molecular weight polyol or low molecular weight polyol can be used.
[0148] Although there are no particular limitations on the high molecular weight polyol, it is preferable that the number average molecular weight is 400 to 8,000, and more preferably 400 to 4,000. If the number average molecular weight is within this range, it is possible to obtain an appropriate viscosity and a good appearance of the release layer. Examples of the high molecular weight polyol include polycarbonate polyol, polyester polyol, polyether polyol, etc. In order to improve the adhesion to the polyester film, polycarbonate polyol is preferred.
[0149] Polycarbonate polyol is obtained by dealcoholization reaction between polyhydric alcohols and carbonate compounds. Examples of polyhydric alcohols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane 1,4-benzenedimethanol, 1,3-benzenedimethanol, 4,4'-naphthalenedimethanol, and 3,4'-naphthalenedimethanol. Examples of the carbonate compound include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, etc., and examples of the polycarbonate polyol obtained by the reaction of these compounds include polyhexamethylene carbonate diol, polycyclohexylene carbonate diol, etc. Among these, polyhexamethylene carbonate diol is preferred from the viewpoint of the adhesion of the release layer to the polyester film.
[0150] Examples of polyester polyols include polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their acid anhydrides and polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-methyl-2,4-pentanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5 ... Examples of the compound include those obtained by the reaction of 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, lactonediols, and the like, and those having a derivative unit of a lactone compound such as polycaprolactone.
[0151] Examples of the polyether polyol include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.
[0152] The low molecular weight polyol is not particularly limited, but examples thereof include those having a number average molecular weight of 60 or more and less than 400. For example, aliphatic diols having 2 to 9 carbon atoms such as ethylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, diethylene glycol, triethylene glycol, and tetraethylene glycol; 1,4-cyclohexane Examples of the diols having an alicyclic structure having 6 to 12 carbon atoms, such as dimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanediol, 1,4-bis(hydroxyethyl)cyclohexane, 2,7-norbornanediol, tetrahydrofuran dimethanol, and 2,5-bis(hydroxymethyl)-1,4-dioxane, as well as dimethylolalkanoic acids, such as 2,2-dimethylolpropanoic acid and 2,2-dimethylolbutanoic acid, and low-molecular-weight polyhydric alcohols, such as trimethylolpropane, pentaerythritol, and sorbitol, are listed. Among these, dimethylolalkanoic acids are preferred from the viewpoint of improving the stability of the aqueous dispersion of the urethane (meth)acrylate compound.
[0153] Examples of the (meth)acrylate compound include monofunctional (meth)acrylates, bifunctional (meth)acrylates, polyfunctional (meth)acrylates, etc. Here, the polyfunctional (meth)acrylate refers to a compound having three or more (meth)acrylate groups in one molecule. The (meth)acrylate compound may be a polymer or a monomer, and is preferably a monomer from the viewpoint of reactivity with the silicone compound.
[0154] The monofunctional (meth)acrylate is not particularly limited, and examples thereof include alkyl (meth)acrylates such as methyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate, hydroxyalkyl (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, and ethoxypropyl (meth)acrylate. Examples of such alkoxyalkyl (meth)acrylates include aromatic (meth)acrylates such as alkoxyalkyl (meth)acrylate, benzyl (meth)acrylate, and phenoxyethyl (meth)acrylate; amino group-containing (meth)acrylates such as diaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; ethylene oxide-modified (meth)acrylates such as methoxyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, and phenylphenol ethylene oxide-modified (meth)acrylate; glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and (meth)acrylic acid.
[0155] The bifunctional (meth)acrylate is not particularly limited, but examples thereof include alkanediol di(meth)acrylates such as 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tricyclodecanedimethylol di(meth)acrylate, bisphenol-modified di(meth)acrylates such as bisphenol A ethylene oxide-modified di(meth)acrylate and bisphenol F ethylene oxide-modified di(meth)acrylate, glycerin di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol di(meth)acrylate, dipentaerythritol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, urethane di(meth)acrylate, and epoxy di(meth)acrylate.
[0156] The polyfunctional (meth)acrylate is not particularly limited, but examples thereof include alkylenoxide-modified trimethylolpropane tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethylene oxide-modified trimethylolpropane tri(meth)acrylate, and propylene oxide-modified trimethylolpropane tri(meth)acrylate, isocyanuric acid-modified tri(meth)acrylates such as ethylene oxide-modified isocyanuric acid tri(meth)acrylate, and ε-caprolactone-modified tris(acryloxyethyl)isocyanurate, pentaerythritol tri(meth)acrylate, and the like. Examples of the alkylene oxide-modified pentaerythritol tetra(meth)acrylate include alkylenoxide-modified pentaerythritol tetra(meth)acrylate such as ethylene oxide-modified pentaerythritol tetra(meth)acrylate, dipentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, tetramethylolmethane ethylene oxide-modified tetra(meth)acrylate, and ethylene oxide-modified pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0157] Among these, from the viewpoint of more efficient crosslinking, bifunctional (meth)acrylate or polyfunctional (meth)acrylate is preferred, polyfunctional (meth)acrylate is more preferred. Specifically, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate is preferred, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(tri)acrylate is more preferred.
[0158] When the present release agent composition contains a compound containing a (meth)acryloyl group, the content of the compound containing a (meth)acryloyl group in the present release agent composition is preferably 1 to 50 mass%, more preferably 1 to 40 mass%, further preferably 2 to 30 mass%, and particularly preferably 2 to 10 mass%, as a ratio of the total non-volatile components in the present release agent composition. By making the content equal to or greater than the above lower limit, the adhesion to the present polyester film can be improved. In addition, by making the content equal to or less than the above upper limit, sufficient releasability can be ensured.
[0159] ((particularly preferred form)) From the viewpoint of obtaining excellent releasability, the present release layer preferably contains a silicone compound as the release agent. Furthermore, from the viewpoint of obtaining excellent adhesion to polyester films, it is preferable that when the release agent contains a silicone compound, the release agent composition further contains a compound containing a (meth)acryloyl group, or that when the release agent contains a long-chain alkyl, the release agent composition further contains a crosslinking agent. Furthermore, from the viewpoint of lowering the air leakage index described below and improving the handling properties, such as the winding properties, of the present laminated polyester film, it is preferable that the present release layer contains a long-chain alkyl group-containing compound as the release agent. In this way, the above particularly preferred embodiments may be appropriately selected depending on the characteristics that are prioritized.
[0160] ((Other ingredients)) In addition to the above components, additives such as binder resins, particles, antifoaming agents, coatability improvers, surfactants, thickeners, organic lubricants, UV absorbers, antioxidants, foaming agents, dyes, pigments, etc. may be appropriately added within the scope of the present invention. Specific embodiments of the binder resin that can be contained in the present release agent composition are the same as those of the binder resin that can be contained in the present resin composition, and all of these can be used. When a silicone compound is used as the release agent, a catalytic amount of a platinum group metal catalyst, a reactive release agent, etc. may be appropriately blended.
[0161] ((solvent)) The release agent composition of the present invention may be diluted with a solvent to form a coating liquid. That is, the release agent composition of the present invention may be applied, for example, to the present polyester film as a liquid coating liquid, and then dried and cured as necessary to form a release layer. Each of the components constituting the present release agent composition (the release agent, the optionally added crosslinking agent and the compound containing a (meth)acryloyl group, other components, etc.) may be dissolved in a solvent or dispersed in a solvent. When the coating liquid is prepared, the concentration of the total non-volatile components of the present release agent composition in the coating liquid is preferably 0.1 to 50% by mass. If the concentration is equal to or higher than the lower limit, a release layer of a desired thickness can be efficiently formed. On the other hand, if the concentration is equal to or lower than the upper limit, the viscosity during coating can be suppressed, thereby improving the appearance of the release layer and increasing the stability in the coating liquid.
[0162] Specific and preferred embodiments of the solvent with which the present release agent composition can be diluted are the same as those of the solvent with which the present resin composition can be diluted, and all of these can be used by reference.
[0163] It can be assumed that the release layer contains unreacted components of the present release agent composition (the release agent, the optionally added crosslinking agent and the compound containing a (meth)acryloyl group, other components, etc.), reacted compounds, or a mixture thereof. The components in the release layer can be analyzed by, for example, TOF-SIMS, ESCA, fluorescent X-rays, or the like.
[0164] <Method of forming release layer> Next, the method for forming the release layer will be described. Specific and preferred aspects of the method for forming the release layer are the same as those of the method for forming the resin layer, and all of these can be used. That is, in the present invention, the release layer is preferably formed by in-line coating, which treats the surface of the polyester film during the film-forming process. In addition, although not limited to the following, for example, in the case of successive biaxial stretching, a method in which a uniaxially stretched film stretched in the longitudinal direction (machine direction) is coated and then stretched in the transverse direction is particularly advantageous.
[0165] The coating amount of the non-volatile component of the release layer is preferably 0.001 to 1.0 g / m 2 , more preferably 0.005 to 0.5 g / m 2 , and more preferably 0.01 to 0.2 g / m 2 If the coating amount is equal to or more than the lower limit, sufficient releasability can be obtained. If the coating amount is equal to or less than the upper limit, deterioration of the coating appearance and insufficient curing of the coating can be suppressed. The coating amount can be calculated from the concentration of non-volatile components in the coating solution, the coating amount before drying derived from the consumption amount of the coating solution, the transverse stretching ratio, and the like. The coating amount of the non-volatile component refers to the coating amount in the present laminated polyester film, and for example, in the case where drying and stretching are performed, it refers to the coating amount after drying and stretching.
[0166] <<<Physical properties of laminated polyester film>>> (Average length of roughness curve element (RSm)) The average length of the roughness curve elements (RSm) on the surface of the resin layer of the present laminated polyester film is 5 μm or more. The average length of the roughness curve element (RSm) is a parameter indicating the average value of the periodic interval between the convex portion and the concave portion in the reference length, and if the average length of the roughness curve element (RSm) is 5 μm or more, the air escape property can be efficiently maintained even when the film is laminated. From this viewpoint, the average length of the roughness curve element (RSm) is preferably 5.3 μm or more, more preferably 5.5 μm or more, even more preferably 5.8 μm or more, and particularly preferably 6.1 μm or more. The upper limit is not particularly limited, but is preferably 10 μm or less.
[0167] The average length of the roughness curve element (RSm) is one of the line roughness parameters (JIS B 0601:2013), where m is the reference length and X is the Si If the length of the contour curve element is:
[0168]
number
[0169] (Kurtosis (Sku)) The kurtosis (Sku) of the resin layer surface of the present laminated polyester film is preferably less than 3. Kurtosis (Sku) is a parameter related to the tip shape of the unevenness. Sku=3 is considered to be a normal distribution. If Sku>3, the height distribution is pointed, i.e., the surface has many sharp unevennesses. If Sku<3, the height distribution of the surface unevenness is flat, i.e., the surface is relatively flat. Therefore, if the kurtosis (Sku) is less than 3, the projections have a flat surface, so that the projection apex is less likely to be crushed when the films are stacked, and air escape properties can be efficiently maintained. From this viewpoint, the kurtosis is preferably 2.9 or less, more preferably 2.8 or less, even more preferably 2.6 or less, particularly preferably 2.4 or less, and especially preferably 2.2 or less. The lower limit is not particularly limited and is 0.1.
[0170] Kurtosis (Sku) is one of the surface roughness parameters (ISO 25178) and can be used to evaluate the peakiness (kurtosis) of the height distribution histogram and is calculated using the following formula (2). If the surface is the XY plane and the height direction is the Z axis, A: the defined area (the entire image), Z(x,y): the height of the image point (x,y) from the surface at height 0, and Sq: the root mean square height (equivalent to the standard deviation of the height distribution), it can be expressed as follows.
[0171]
number
[0172] (Roughness curve load length ratio (Rmr)) The load length ratio (Rmr(70)) of the roughness curve at a cutting level of 70% on the resin layer surface of the present laminated polyester film is preferably 75% or less. The load length ratio (Rmr(70)) is an effective index for expressing the unevenness distribution of an uneven structure. For example, a large concave distribution will have a small load length ratio (Rmr(70)) value, and a large convex distribution will have a large load length ratio (Rmr(70)) value. If the load length ratio (Rmr(70)) is 75% or less, it indicates that an appropriate fine uneven structure is formed, and when the film is wound into a roll, the gaps between the film become larger, making it easier for air to escape, and improving winding characteristics, etc. From this viewpoint, the load length ratio (Rmr(70)) is preferably 70% or less, more preferably 65% or less, and even more preferably 60% or less. The lower limit is not particularly limited and is about 1%, preferably 10% or more, more preferably 15% or more, even more preferably 20% or more, and even more preferably 25% or more.
[0173] The load length ratio (Rmr(50)) of the roughness curve at a cutting level of 50% on the resin layer surface of the laminated polyester film is preferably 53% or less, more preferably 50% or less, even more preferably 45% or less, and even more preferably 42% or less. The lower limit is not particularly limited and is about 1%, preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. Furthermore, the load length ratio (Rmr(80)) of the roughness curve at a cutting level of 80% on the resin layer surface of the laminated polyester film is preferably 75% or less, more preferably 70% or less, even more preferably 65% or less, and particularly preferably 60% or less. The lower limit is not particularly limited and is about 5%, preferably 15% or more, more preferably 20% or more, even more preferably 25% or more, and even more preferably 30% or more. The load length ratio (Rmr(90)) of the roughness curve at a cutting level of 90% on the resin layer surface of the laminated polyester film is preferably 80% or less, more preferably 75% or less, even more preferably 70% or less, and even more preferably 65% or less. The lower limit is not particularly limited and is about 10%, preferably 15% or more, more preferably 20% or more, even more preferably 25% or more, and even more preferably 30% or more. When the surface shape parameter is equal to or greater than the lower limit, the resin layer has a fine surface structure, and the laminated polyester film has good handleability. When the surface shape parameter is equal to or less than the upper limit, the resin layer has a sufficiently fine uneven structure.
[0174] (Arithmetic mean roughness (Ra)) The arithmetic mean roughness (Ra) of the resin layer surface of the present laminated polyester film measured by a scanning probe microscope is preferably 10 nm or more, more preferably 30 nm or more, even more preferably 50 nm or more, even more preferably 80 nm or more, and particularly preferably 100 nm or more. The upper limit is not particularly limited, but is preferably 600 nm or less, more preferably 400 nm or less, even more preferably 300 nm or less, even more preferably 250 nm or less, and particularly preferably 200 nm or less. When the arithmetic mean roughness (Ra) is the above lower limit or more, the present resin layer can be said to have a fine surface structure, and the present laminated polyester film can be handled well. When the arithmetic mean roughness (Ra) is the above upper limit or less, the present resin layer can be said to have a sufficiently fine uneven structure.
[0175] The arithmetic mean roughness (Ra) is one of the line roughness parameters (JIS B 0601:2013) and represents the average height difference from the average surface. That is, when a portion of the reference length L is sampled, the average line of this sampled portion is taken as the x-axis, the direction of the longitudinal magnification is taken as the y-axis, and the roughness curve is expressed as y = Z(x), it can be obtained from the following formula (3).
[0176]
number
[0177] (Ten-point average roughness (Rzjis)) In addition, the ten-point average roughness (Rzjis) of the resin layer surface of the present laminated polyester film measured by a scanning probe microscope is preferably 60 nm or more, more preferably 100 nm or more, even more preferably 150 nm or more, even more preferably 200 nm or more, and particularly preferably 250 nm or more. The upper limit is not particularly limited, but is preferably 800 nm, more preferably 600 nm, even more preferably 500 nm, even more preferably 450 nm, and particularly preferably 400 nm. If the ten-point average roughness (Rzjis) is equal to or greater than the lower limit, the present resin layer can be said to have a sufficient uneven structure. If the ten-point average roughness (Rzjis) is equal to or less than the upper limit, the present resin layer can be said to have a sufficiently fine uneven structure.
[0178] Ten-point average roughness (Rzjis) is one of the line roughness parameters (JIS B 0601:2013) and represents the sum of the average of the five greatest peak heights (Zp) and the average of the five greatest valley depths (Zv) on a profile curve over a reference length L, and is calculated using the following formula (4).
[0179]
number
[0180] (Root-mean-square gradient (Sdq)) The root mean square gradient (Sdq) of the resin layer surface of the laminated polyester film is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.25 or more, even more preferably 0.3 or more, and particularly preferably 0.35 or more. On the other hand, the root mean square gradient (Sdq) is preferably 3 or less, more preferably 2 or less, even more preferably 1.5 or less, even more preferably 1 or less, and particularly preferably 0.8 or less. If the root mean square gradient (Sdq) is equal to or more than the lower limit, the difference between the peaks and valleys of the uneven structure is clear, and the air escape property can be further improved. Also, if the root mean square gradient (Sdq) is equal to or less than the upper limit, it is easy to suppress coarse protrusions.
[0181] The root mean square gradient (Sdq) is one of the surface roughness parameters (ISO 25178) and is calculated by the following formula (5). The root mean square gradient (Sdq) represents the average magnitude of the local gradient (slope) of the uneven surface shape, and a larger value indicates a steeper surface.
[0182]
number
[0183] (Developed interface area ratio (Sdr)) In addition, the developed interface area ratio (Sdr) of the resin layer surface of the present laminated polyester film is preferably 0.5% or more, more preferably 3% or more, even more preferably 5% or more, even more preferably 7% or more, and particularly preferably 9% or more. On the other hand, the developed interface area ratio (Sdr) is preferably 60% or less, more preferably 40% or less, even more preferably 30% or less, even more preferably 25% or less, and particularly preferably 20% or less. If the developed interface area ratio (Sdr) is the above lower limit or more, a fine surface structure can be formed, thereby improving winding properties. In addition, if the developed interface area ratio (Sdr) is the above upper limit or less, undulations are appropriately suppressed, and coarse protrusions and the like can be prevented.
[0184] The developed interface area ratio (Sdr) is one of the surface roughness parameters (ISO 25178) and is calculated by the following formula (6). The developed interface area ratio (Sdr) represents the degree to which the developed area (surface area) of a defined region has increased relative to the area of the defined region, i.e., the rate of increase in surface area; the denser and more rugged the surface shape is, the larger the value.
[0185]
number
[0186] The average length of the roughness curve (RSm), kurtosis (Sku), load length ratio (Rmr), arithmetic mean roughness (Ra), ten-point average roughness (Rzjis), root mean square gradient (Sdq), and developed interface area ratio (Sdr) can be adjusted by the composition and content in the resin composition, the method for forming the resin layer, and various conditions in the formation process, etc. In adjusting the composition, for example, when using a binder resin (A) and / or a crosslinking agent (B), it is preferable to select the type of the binder resin (A) and / or the crosslinking agent (B) in consideration of the type, average particle size, content, etc. of the particles to be blended. In the present invention, as described above, it is preferable that fine protrusions are formed by particles or that the stretchability of the resin composition is intentionally made inferior. Therefore, for example, the (A) binder resin may be appropriately selected. Specifically, it is preferable to adopt a resin having poor stretchability as the (A) binder resin, that is, a resin that is less likely to follow stretching than normal during stretching, especially during transverse stretching. Specifically, in consideration of the temperature during stretching, it is preferable to adopt the (A) binder resin having a glass transition temperature that matches the desired stretchability. On the other hand, when using the (A) binder resin having good stretchability, it is preferable to increase the amount of particles to be blended. In other words, in consideration of the stretchability of the (A) binder resin, it is preferable to appropriately adjust the type of particles and the average particle size of the particles to be blended. It is also preferable to use a crosslinking agent (B) whose curing reaction proceeds easily even at a relatively low temperature. If the curing reaction of the crosslinking agent proceeds or is completed at the stage of stretching the film, particularly the stage of transverse stretching, it is presumed that the coating film will have difficulty following the stretching, and the resin layer formed from the present resin composition will be prone to cracking. From the viewpoint of forming a fine surface shape and an uneven structure, it is also preferable to use particles having a relatively small average particle size. The average particle size of the particles may be appropriately selected in consideration of the types of (A) binder resin and (B) crosslinking agent to be blended as necessary.
[0187] The kurtosis (Sku), load length ratio (Rmr), arithmetic mean roughness (Ra), ten-point mean roughness (Rzjis), root mean square gradient (Sdq) and developed interface area ratio (Sdr) of the resin layer surface can be measured by the method described in the Examples using an atomic force microscope (scanning probe microscope). Measurements using an atomic force microscope (scanning probe microscope) can capture finer surface structures, making it possible to obtain values that strongly reflect the effects of the resin layer.
[0188] (Arithmetic mean height (Sa)) The arithmetic mean height (Sa) of the resin layer surface of the present laminated polyester film is preferably more than 25 nm, more preferably 30 nm or more, even more preferably 35 nm or more, and even more preferably 40 nm or more. On the other hand, the arithmetic mean height (Sa) is preferably 300 nm or less, more preferably 250 nm or less, even more preferably 200 nm or less, and even more preferably 170 nm or less. If the arithmetic mean height (Sa) is within this range, it is easy to reduce extremely large unevenness while having a fine uneven shape. Therefore, for example, the handleability of the present laminated polyester film can be ensured, and wrinkles when wound into a roll can be suppressed. For example, when the film is used as a support for a ceramic green sheet in the manufacturing process of a laminated ceramic capacitor, and a release layer or ceramic layer is provided on the film surface opposite to the surface on which the present resin layer is provided, it is easy to prevent the protrusions on the surface of the present resin layer from being transferred to the ceramic layer or the ceramic layer from being destroyed.
[0189] Arithmetic mean height (Sa) is one of the surface roughness parameters (ISO 25178), and is a three-dimensional extension of the two-dimensional Ra (arithmetic mean roughness of lines). It is calculated by dividing the volume enclosed by the surface profile curve and the mean surface by the measured area, and is calculated using the following formula (7). If the surface is the XY plane and the height direction is the Z axis, A is the defined area (the entire image), and Z(x,y) is the height of the image point (x,y) from the plane with height 0, it can be expressed as follows.
[0190]
number
[0191] (Maximum mountain height (Sp)) The maximum peak height (Sp) of the resin layer surface of the present laminated polyester film is preferably 2000 nm or less, more preferably 1500 nm or less, even more preferably 1200 nm or less, even more preferably 1000 nm or less, and particularly preferably 900 nm or less. On the other hand, the maximum peak height (Sp) is preferably more than 500 nm, more preferably 550 nm or more, even more preferably 570 nm or more, and even more preferably 600 nm or more. If the maximum peak height (Sp) is equal to or less than the upper limit value, protrusions can be reduced. Therefore, for example, when the present laminated polyester film is used as a support for a ceramic green sheet in the manufacturing process of a laminated ceramic capacitor, and a release layer or a ceramic layer is provided on the film surface opposite to the surface on which the present resin layer is provided, it becomes easy to prevent the protrusions on the surface of the present resin layer from being transferred to the ceramic layer or the ceramic layer from being destroyed. In addition, if the maximum peak height (Sp) is equal to or more than the lower limit value, the handleability of the present laminated polyester film can be ensured, and wrinkles can be easily suppressed when the film is wound into a roll.
[0192] The maximum peak height (Sp) is one of the surface roughness parameters (ISO 25178) and represents the maximum value of the height from the average plane of the surface, and is expressed by the following formula (8).
[0193]
number
[0194] The arithmetic mean height (Sa) and maximum peak height (Sp) of the resin layer surface can be adjusted by the composition and content in the resin composition, the method of forming the resin layer, and various conditions in the forming process, etc. Specifically, the same method as the method of adjusting the average length of the roughness curve element (RSm), kurtosis (Sku), load length ratio of the roughness curve (Rmr), arithmetic mean roughness (Ra), ten-point average roughness (Rzjis), root-mean-square gradient (Sdq), and developed interface area ratio (Sdr), etc., may be adopted. The arithmetic mean height (Sa) and maximum peak height (Sp) of the resin layer surface can be measured by a non-contact surface roughness meter that utilizes optical interference, specifically, by the method described in the Examples. Measurement by this method makes it possible to obtain values that reflect a larger area of the present laminated polyester film.
[0195] (Tape peeling force) The tape peel strength of the release layer of the present laminated polyester film is preferably 500 mN / cm or less, more preferably 400 mN / cm or less, even more preferably 300 mN / cm or less, and particularly preferably 200 mN / cm or less. If the tape peel strength is 500 mN / cm or less, the present laminated polyester film can be said to have sufficient releasability. The lower limit is not particularly limited, and is about 0.1 mN / cm.
[0196] (Static friction coefficient) The static friction coefficient between the resin layer surface and the release layer surface of the present laminated polyester film is preferably 1 or less, more preferably 0.8 or less, further preferably 0.6 or less, and particularly preferably 0.4 or less. When the present laminated polyester film is wound into a roll, the surface of the resin layer and the surface of the release layer come into contact with each other, and therefore the static friction coefficient between the surfaces of the resin layer and the release layer is important. Therefore, when the static friction coefficient is within this range, the uneven structure of the present resin layer provides good slipperiness, improving the handleability of the present laminated polyester film. The static friction coefficient can be measured by the method described in the Examples.
[0197] (Air Leak Index) The air leakage index can be used as an index for evaluating the handling properties, such as the winding properties, of the present laminated polyester film. If the air leakage index is low, the air trapped when the present laminated polyester film is wound up can be easily released, and defects in the roll appearance, such as wrinkles and uneven edges, can be prevented. On the other hand, if the air leakage index is high, the trapped air can escape after a sufficient amount of time has passed, especially during transportation, causing problems such as the film shifting in the direction of the winding core or scratches due to the shifting. Such defects do not occur with the present laminated polyester film.
[0198] The air leakage index is preferably 50000 seconds or less, more preferably 40000 seconds or less, even more preferably 350000 seconds or less, and even more preferably 30000 seconds or less. If the air leakage index is equal to or less than the upper limit, the handling property tends to be good. The air leakage index can be improved by the uneven structure of the resin layer, and can also be improved by the roughness of the smooth surface of the polyester film. Specifically, it is preferable that the arithmetic mean height (Sa) of the polyester film surface on the side opposite to the side on which the resin layer is formed (i.e., the smooth side) is 15 nm or less, and / or the maximum peak height (Sp) is 800 nm or less. Here, the opposite side is preferably the film surface used for processing when the laminated polyester film is used for various applications such as a release film for forming a green sheet for a laminated ceramic capacitor, an interlayer insulating resin release film, and a release film for dry film resist, and for example, various materials may be coated or laminated, as described later. Furthermore, when more precise processing is required, it is more preferable that the arithmetic mean height (Sa) of the polyester film surface on the opposite side (i.e., the smooth side of the film used for processing) is 9 nm or less, and / or the maximum peak height (Sp) is 500 nm or less. In this way, when the smooth side of the film is extremely smooth, more precise processing is possible by utilizing the smoothness of the film, and the uneven structure of the resin layer improves the air leakage index to the above range, improving the winding property and improving the handling property of the laminated polyester film. Thus, the air leakage index depends on the smoothness of the polyester film surface on the side opposite to the side on which the resin layer is formed. Even when smoothness is required of the polyester film, the uneven structure of the resin layer can improve the handling properties. The air leakage index can be measured by the method described in the Examples.
[0199] <<<Applications of laminated polyester film>>> The resin layer of the laminated polyester film is composed of a resin composition containing a certain amount of a specific compound, and has a specific roughness structure, which allows it to express a fine uneven structure. Specifically, the resin layer surface has a characteristic that the average length of the roughness curve element (RSm) is 5 μm or more. This design concept has made it possible to precisely control the fine uneven structure, which was difficult to achieve with conventional particle-kneaded film manufacturing methods. In addition, the specific roughness structure has made it possible to improve the ease of air escape even in a thin film, making it possible to provide a laminated polyester film with excellent handling properties.
[0200] The present laminated polyester film can be used for various applications for the purpose of improving the handleability, and the applications are not particularly limited. In particular, as described above, since the film has a fine uneven structure, when used for sheet molding, it has the advantage that it exhibits good winding properties and is less likely to cause wrinkles even when a highly smooth film is wound into a roll, and it can be suitably used as a release film for sheet molding. Examples of the release film for sheet molding include various release applications such as green sheet molding for multi-layer ceramic capacitors (MLCCs), interlayer insulating resins, dry film resists (DFRs), and multilayer circuit boards. In release applications, the laminated polyester film is used, for example, as a support. In particular, the laminated polyester film can be suitably used as a support for ceramic green sheets in the manufacturing process of multi-layer ceramic capacitors, particularly multi-layer ceramic capacitors for automobiles. The sheet molding release film may be used, for example, in a process for forming various sheets such as green sheets by applying or laminating various materials on at least one side of the film. For example, a method for producing a ceramic green sheet may be used in which a slurry containing a ceramic component is applied to the side (release layer) opposite to the resin layer of the laminated polyester film of the present invention. That is, various materials are preferably applied or laminated on the release layer side.
[0201] For example, a multilayer ceramic capacitor (MLCC) is manufactured using this laminated polyester film as follows. For example, a ceramic slurry containing a ceramic component and a binder resin is applied to the laminated film, preferably on the surface opposite to the resin layer of the laminated polyester film, and dried to prepare a ceramic green sheet (dielectric sheet). Then, electrodes are printed on the laminated film by screen printing or the like to form internal electrodes, and after drying, the printed ceramic green sheet is peeled off from the release film (the laminated polyester film), and a large number of such green sheets are laminated. The laminated green sheets are pressed to be integrated, and then cut into individual chips. Then, the internal electrodes and dielectric layers are sintered in a firing furnace to obtain a multilayer ceramic capacitor. Thus, the laminated polyester film of the present invention is preferably used as a support for ceramic green sheets in the production process of a laminated ceramic capacitor.
[0202] <<<Term explanation>>> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES
[0203] The present invention will now be described in further detail with reference to examples. However, the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention.
[0204] <Evaluation method> (1) Intrinsic viscosity (IV) of polyester 1 g of polyester from which components incompatible with the polyester had been removed was precisely weighed out, dissolved in 100 mL of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and the viscosity was measured at 30 °C using a viscosity measuring device "VMS-022UPC·F10" (manufactured by Rigo Co., Ltd.).
[0205] (2) Rough structure of the resin layer Measurements were carried out using a scanning probe microscope (Shimadzu Corporation, SPM-9700) under the following conditions. Tip: Silicon cantilever Scanning mode: Dynamic mode Scanning range: 25μm×25μm Scan speed: 0.8Hz Pixel count: 512 x 512 data points From the obtained data, the cross-sectional shape of a width of 25 μm was observed, and if there were multiple convex or concave parts with a step difference of more than 10 nm in more than 80% of the positions, it was judged as "present" of an uneven structure, and if multiple convex or concave parts could not be confirmed, it was judged as "absent" of an uneven structure.
[0206] (3) Arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis) of the resin layer surface From the data of the scanning probe microscope measured by the method (2) above, a cross-sectional analysis of 25 μm width was performed parallel to the tenter stretching direction (i.e., the transverse direction) to obtain the arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis). Cross-sectional analysis data was obtained at 10 points at equal intervals in the film formation direction (i.e., the longitudinal direction), and these were averaged to obtain the arithmetic mean roughness (Ra) and ten-point mean roughness (Rzjis).
[0207] (4) Load length ratio of the resin layer surface (Rmr(70)) The cross-sectional analysis was performed using a scanning probe microscope in the same manner as in (3) above, and the load length ratio at the 70% cut level (Rmr(70)) was calculated. Cross-sectional analysis data was obtained at 10 points at equal intervals in the film formation direction (i.e., the machine direction), and the average was calculated. Similarly, the load length ratio at a cut level of 50% (Rmr(50)), the load length ratio at a cut level of 80% (Rmr(80)), and the load length ratio at a cut level of 90% (Rmr(90)) were obtained.
[0208] (5) Kurtosis (Sku), root mean square gradient (Sdq) and developed interface area ratio (Sdr) of the resin layer surface Image data obtained from the scanning probe microscope data measured by the method in (2) above was analyzed using the image analysis software SPIP6.2.5 Image Metrology to calculate the kurtosis (Sku), root mean square gradient (Sdq), and developed interface area ratio (Sdr).
[0209] (6) The arithmetic mean height (Sa), maximum peak height (Sp), and mean length of the roughness curve (RSm) of the resin layer surface The film surface was measured using a non-contact surface / layer cross-sectional shape measurement system VertScan (registered trademark) R550GML manufactured by Ryoka Systems Co., Ltd., with a CCD camera: SONY HR-501 / 3', objective lens: 20x, lens barrel: 1X Body, zoom lens: No Relay, wavelength filter: 530 white, measurement mode: Wave, in an area of 640 μm x 480 μm. The arithmetic mean height (Sa), maximum peak height (Sp) and average length of the roughness curve (RSm) were calculated as an average of 10 points using the output from a fourth-order polynomial correction.
[0210] (7) Coating retention rate A BEMCOT ("M-3II" manufactured by Asahi Kasei Fibers Corporation) impregnated with 4 mL of methyl ethyl ketone was attached to a rubbing tester (manufactured by Ohira Rika Kogyo Co., Ltd.) and rubbed five times on the resin layer surface of the sample film with an arm load of 680 g. The resin layer surface before and after treatment was measured by X-ray fluorescence analysis (XRF) to measure the amount of components derived from the resin layer. The retention rate of the coating was calculated by the following formula. Coating retention rate (%) = (amount of resin layer component after treatment / amount of resin layer component before treatment) x 100
[0211] (8) Coefficient of static friction The static friction coefficient between the resin layer surface and the release layer surface of the laminated polyester film was determined by the following method. A film was attached to a smooth metal plate with a width of 10 mm and a length of 100 mm so that the release layer surface was the upper surface. A film cut to a width of 18 mm and a length of 120 mm was placed on top of the film so that the surface on which the resin layer was provided was the lower surface, and a metal pin with a diameter of 8 mm was pressed onto the film, and the metal pin was slid in the longitudinal direction of the glass plate with a load of 30 g at 40 mm / min to measure the friction force, and the maximum value immediately after the sliding was evaluated as the static friction coefficient. The measurement was performed in an atmosphere of room temperature 23±1°C and humidity 50±0.5%RH. The number of measurements (N) was three, and the average value was used. Static friction coefficient (μs) = Fs / weight load (In the above formula, the unit of Fs is g force, and the unit of weight load is g force.)
[0212] (9) Air leakage index A DigiBec smoothness tester (manufactured by Toyo Seiki Co., Ltd., "DB-2") was used to measure in accordance with JIS P8119:1998 under an atmosphere of 23°C and 50%RH. The pressure of the pressurizing device was 100 kPa, and the vacuum container had a volume of 38 mL. The time it took for 1 mL of air to flow, i.e., the time (seconds) for the pressure inside the container to change from 50.7 kPa to 48.0 kPa, was measured, and the air leakage index was calculated by multiplying the number of seconds obtained by the measurement. The sample size of the test film was 70 mm square, and 20 sheets of the test film were stacked so that the front and back of the test film overlapped to form a test laminate film. A 5mm hole was made in the center of the test laminate film, and the air leakage index was measured as described above. The higher the air leakage index value, the longer it takes for air to leak through the gaps between the films, indicating that the films are more closely attached to each other, and therefore the greater the risk of wrinkles occurring when the film is rolled up.
[0213] <Materials used> In the examples and comparative examples, pellets of polyethylene terephthalate homopolymer (intrinsic viscosity: 0.64 dL / g) were used as the polyester.
[0214] The resin compositions for forming the resin layers were prepared by stirring and mixing the compositions shown in Table 1 below, and diluting the resulting resin compositions with water to prepare coating solutions A1 to A8. The compounds used are as follows. A coating solution for forming a release layer was prepared according to the composition shown in Table 2 below. The compounds used are as follows.
[0215] [Component (A): Binder resin (IA)] Aqueous dispersion of polyester resin copolymerized with the following composition Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / diethylene glycol = 92 / 8 / / 80 / 20 (mol%)
[0216] [Component (A): Binder resin (IB)] Aqueous dispersion of polyester resin copolymerized with the following composition Monomer composition: (acid component) 2,6-naphthalenedicarboxylic acid / sebacic acid / 5-sodium sulfoisophthalic acid / (diol component) ethylene glycol / hexanediol / diethylene glycol = 37 / 11 / 3 / / 27 / 17 / 5 (mol%)
[0217] [Component (A): Binder resin (IC)] Aqueous dispersion of polyester resin copolymerized with the following composition Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol component) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%)
[0218] [Component (A): Binder resin (ID)] Aqueous dispersion of polyester resin copolymerized with the following composition Monomer composition: (acid component) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol component) ethylene glycol / neopentyl glycol = 49 / 48 / 3 / / 50 / 50 (mol%)
[0219] [Component (B): Crosslinking agent (II)] Polyisocyanate derivative of hexamethylene diisocyanate
[0220] [Particle (IIIA)] Spherical silica particles with an average diameter of 11 nm [Particle (IIIB)] Silica particles with an average particle size of 5 nm [Particle (IIIC)] Silica particles with an average particle size of 200 nm
[0221] [Release agent (IVA)] Aqueous dispersion of vinyl-containing polydimethylsiloxane with a vinyl group content of 0.16 mmol / g (emulsifier: nonionic surfactant) [Release agent (IVB)] Aqueous dispersion of hydrogen-containing polydimethylsiloxane with a Si-H group content of 7.8 mmol / g (emulsifier: nonionic surfactant)
[0222] Example 1 The polyester pellets were melted at 285° C., extruded onto a cooling roll set at 40° C., and cooled and solidified to obtain an unstretched sheet. Next, this film was stretched 3.5 times in the longitudinal direction while passing through a group of heated rolls at 85° C. to obtain a uniaxially stretched film. On one side of this uniaxially stretched film, a coating solution A1 having the composition shown in Table 1 below was applied in an amount (after drying and stretching) of 0.10 g / m 2 On the other side, coating solution B1 having the composition shown in Table 2 below was applied in an amount of 0.06 g / m2 (after drying and stretching). 2 The film was then introduced into a tenter stretching machine, stretched 4.4 times in the width direction at 100°C, and further heat-treated at 235°C, followed by 2% relaxation in the width direction to obtain a laminated polyester film with a thickness of 31 μm. The evaluation results are shown in Table 3.
[0223] (Examples 2 to 6) A laminated polyester film was obtained in the same manner as in Example 1, except that the coating solutions shown in Tables 1 and 2 were used and the coating amounts (after drying and stretching) were set to those shown in Table 3. The evaluation results are shown in Table 3. Fig. 1 shows an image of the resin layer surface observed by a scanning probe microscope for the laminated polyester film of Example 6. From the image in Fig. 1, it can be seen that a fine uneven structure is formed on the resin layer surface.
[0224] Comparative Example 1 Except for not providing a resin layer and a release layer, a polyester film was obtained in the same manner as in Example 1. The evaluation results are shown in Table 3.
[0225] Comparative Example 2 A polyester film having a resin layer was obtained in the same manner as in Example 1, except that the coating solution shown in Table 1 was used, the coating amount (after drying and stretching) was set to the coating amount shown in Table 3, and no release layer was provided. The evaluation results are shown in Table 3.
[0226] (Comparative Examples 3 and 4) A polyester film having a release layer was obtained in the same manner as in Example 1, except that the coating solutions shown in Tables 1 and 2 were used and the coating amounts (after drying and stretching) were set to the amounts shown in Table 3. The evaluation results are shown in Table 3.
[0227] [Table 1]
[0228] [Table 2]
[0229] [Table 3]
[0230] As shown in the results of Table 3, the laminated polyester film of the present invention has an air leakage index of 50,000 seconds or less, which indicates that it has excellent air escape properties. In addition, it has an extremely low static friction coefficient and good slip properties. Therefore, it is clear that the laminated polyester film of the present invention has good winding properties and is a film with excellent productivity. In addition, since the resin layer has excellent coating film retention, the performance of the laminated polyester film is not impaired due to peeling or falling off of the coating film, and the production process is not contaminated by fallen coating film. On the other hand, the polyester film of Comparative Example 1, which does not have a resin layer or a release layer, has an extremely high air leakage index and is therefore problematic in winding properties. Also, the laminated polyester films of Comparative Examples 2 to 4 have a higher air leakage index than the laminated polyester film of the present invention, and therefore are clearly inferior in winding properties. [Industrial Applicability]
[0231] Since the resin layer surface of the laminated polyester film of the present invention has a fine surface structure, when the film is used for forming a sheet, the extremely smooth film exhibits good winding properties and is less likely to wrinkle even when wound into a roll. In addition, since the resin layer of the laminated polyester film of the present invention can be made thin, it is also possible to accommodate thin and long laminated polyester films, which can contribute to improving productivity by reducing the frequency of changing product rolls during processing. Therefore, the laminated polyester film of the present invention can be suitably used as a release film for sheet molding having excellent surface smoothness, and is of great industrial utility.
Claims
1. A laminated polyester film having a resin layer formed from a resin composition on at least one side of the polyester film, the resin layer containing particles, and the average length (RSm) of the roughness curve element of the surface of the resin layer being 5 μm or more.
2. The laminated polyester film according to claim 1 , wherein the resin layer surface has a kurtosis (Sku) of less than 3.
3. The laminated polyester film according to claim 1 , wherein the content of the particles in the resin layer is 10% by mass or more.
4. The laminated polyester film according to claim 1 , wherein the resin composition comprises a binder resin (A).
5. The laminated polyester film according to claim 1 , wherein the resin composition comprises a crosslinking agent (B).
6. The laminated polyester film according to any one of claims 1 to 5, wherein a load length ratio (Rmr(70)) of a roughness curve at a cutting level of 70% on the surface of the resin layer is 75% or less when measured with a scanning probe microscope.
7. The laminated polyester film according to any one of claims 1 to 5, wherein the resin layer has an uneven structure.
8. 6. The laminated polyester film according to claim 1, wherein the resin layer has a surface having an arithmetic average roughness (Ra) of 10 nm or more as measured by a scanning probe microscope.
9. 6. The laminated polyester film according to claim 1, wherein the ten-point average roughness (Rzjis) of the surface of the resin layer measured by a scanning probe microscope is 60 nm or more.
10. The laminated polyester film according to any one of claims 1 to 5, wherein the root mean square gradient (Sdq) of the resin layer surface is 0.1 or more.
11. The laminated polyester film according to any one of claims 1 to 5, wherein a developed interface area ratio (Sdr) of the resin layer surface is 0.5% or more.
12. The laminated polyester film according to any one of claims 1 to 5, wherein the resin layer has a surface arithmetic mean height (Sa) of more than 25 nm.
13. The laminated polyester film according to any one of claims 1 to 5, wherein the resin layer surface has a maximum peak height (Sp) of more than 500 nm.
14. The laminated polyester film according to any one of claims 1 to 5, which has an air leakage index of 50,000 seconds or less.
15. The laminated polyester film according to any one of claims 1 to 5, wherein the particles have an average particle size of 1 to 100 nm.
16. 6. The laminated polyester film according to claim 1, wherein the particles contain at least one selected from the group consisting of silica, zirconium oxide, and titanium oxide.
17. 5. The laminated polyester film according to claim 4, wherein the binder resin (A) comprises at least one resin selected from the group consisting of polyester resins, (meth)acrylic resins, and polyurethane resins.
18. The (B) crosslinking agent is a melamine compound. The laminated polyester film according to claim 5 .
19. The laminated polyester film according to any one of claims 1 to 5, further comprising a release layer on a surface opposite to the resin layer.
20. 20. The laminated polyester film according to claim 19, wherein the release layer is formed from a release agent composition containing a release agent, and the release agent contains at least one kind selected from the group consisting of a silicone compound and a long-chain alkyl group-containing compound.
21. The laminated polyester film according to any one of claims 1 to 5, which is used as a support for a ceramic green sheet in a production process of a laminated ceramic capacitor.
22. 6. Use of the laminated polyester film according to claim 1 as a support for a ceramic green sheet in a process for producing a laminated ceramic capacitor.
23. A method for producing a ceramic green sheet, comprising coating a slurry containing a ceramic component on a surface of the laminated polyester film according to any one of claims 1 to 5 opposite to the resin layer.
Citation Information
Patent Citations
Easy slip composite polyester film
JP2000211082A
Release film for molding ceramic sheet
JP2015033811A